From QbD to Explainable AI: Interpretable Random Forest Surrogates for Design Space Understanding of Voriconazole–β-Cyclodextrin Inclusion Complexes - Sonal Solanki; Garima Kumari; Nikunj Solanki; Diksha Jindal; G. Usha Kiranmai; Snehal Chakorkar; Arnabjyoti Deva Sarma; Narender Boggula; Sreekanth Thota; Manisha Zaware; Ashok Dalimbe (Journal of Pharmaceutical Innovation, 2027)

Development and Validation of a Green Analytical QbD-Based RP-HPLC Method for Quantification of Epigallocatechin Gallate - Garima; Pankaj Popli; Rajan Swami; Neeraj Mittal (Journal of Pharmaceutical Innovation, 2027)

Marker-trait associations for ideotypic traits in pigeonpea (Cajanus cajan L.) - Garima Yadav; Satheesh Naik SJ; Abhishek Bohra; Prakash G. Patil; Shefali Tyagi; Jyotirmay Dubey; Aravind K. Konda; Khela Ram Soren; Meenal Rathore; Girish Prasad Dixit; Shanmugavadivel PS (Molecular Biology Reports, 2026)

Harnessing Lactiplantibacillus plantarum as an anti-fungal candidate against drug resistant Candida albicans - Garima; Shashi Chopra; Sumanpreet Kaur (Molecular Biology Reports, 2026)

Chronic Di(2-ethylhexyl) phthalate and diisononyl phthalate exposure impairs uterine endometrial glycogen metabolism in mice - Pedram Zarei; Isabella Raneri; Garima Thapa; Adriana Andrus; Sarah Ibrahim; Mary J. Laws; Jodi A. Flaws; Romana A. Nowak; Matthew Dean (Reproductive Toxicology, 2026)

Exploring the Potential of Zinc, Vitamin D, and Ascorbate for Enhancing COVID-19 Resilience - Sabina Yasmin; Rani Mansuri; Meenakshi Dhanawat; Garima Malik; Mukta Rani; Surabhi Singh; Eman Shorog; Md Sayeed Akhtar; Bader Yahya Alaskar; Anupama Diwan; Md Yousuf Ansari (Next Research, 2026)

Sustained-release fertilizers for nutrient-use efficiency and environmental resilience: A critical and integrative review - Vivek Kumar Dhiman; Rakesh Kumar; Babit Kumar Thakur; Vinay Kumar Dhiman; Mukul Sharma; Prashant Sharma; Garima Rana; Ritesh Verma; Devendra Singh (Journal of Environmental Chemical Engineering, 2026)

Formulation, Optimization and Characterization of Acetazolamide-Loaded Solid Lipid Nanoparticles for Glaucoma Treatment: In-Vitro and In-Vivo Study - Shuchi Goyal; Ankur; Garima; Rajan Swami; Neeraj Mittal (AAPS PharmSciTech, 2026)

Acitretin shows promising potential in Alzheimer’s disease: retinoid-driven modulation of amyloid processing, neuroinflammation, and translational prospects - Varun Sharma; Kanika Vashisht; Garima Choudhary; Vaishali Choudhay; Vandana Bhatia; Mahendra Singh Ashawat; Ashish Baldi; Shiv Kumar Kushawaha (Inflammopharmacology, 2026)

The multimethod absolute paleointensity approach of Eocene dykes from Ladakh Himalaya: Implications for the paleofield strength in Eocene - Manan Singh; B.V. Lakshmi; K. Deenadayalan; Pradnya Mohite; Garima Shukla; A.P. Dimri (Physics of the Earth and Planetary Interiors, 2026)

Modeling the impact of nature-based solutions on dry season water availability: exploration of spatio-temporal configurations - Garima Mandavya; Sadie McEvoy; Tolulope Odunola; Umit Taner; Xi Chen; Drew McAvoy; Koen Verbist; Patrick Ray (Journal of Hydrology, 2026)

Zebrafish models for genetic and molecular analysis of human pigmentation disorders - Rajbala Verma; Pooja Meena; Garima Awasthi; Mahipal Singh Sankhla; Muhammad Mubashshir; Vivek Kumar; Chandra Shekhar Yadav; Kumud Kant Awasthi (Ecological Genetics and Genomics, 2026)

The role of nanoparticles and nanotechnologies in regulating metal(loid) accumulation in rice (Oryza sativa L.) and wheat (Triticum aestivum L.) - Nandini Chauhan; Garima Awasthi; Kumud Kant Awasthi; Anjali Awasthi; Anuj Sharma; Rajeev Kumar; Yogesh Kumar; Mahipal Singh Sankhla (Physiology and Molecular Biology of Plants, 2026)

Establishment of an efficient in vitro regeneration and Agrobacterium-mediated transformation system in elite northern plain barley (Hordeum vulgare L.) cv. DWRB 160 - Shalu Yadav; Dinesh Kumar; Alka Jangra; Garima Sharma; Santosh Kumar Bishnoi; Vinod Chhokar (Cereal Research Communications, 2026)

Correction: Quercetin Ameliorates Oxidative Stress, Inflammation and Metabolic Dysregulation in a D-Galactose-Induced Ageing Rat Model - Sakshi Jaiswal; Akanksha Singh; Garima Yadav; Nitin Mishra; Sandeep Yadav; Syed Ibrahim Rizvi (Indian Journal of Clinical Biochemistry, 2026)

Postnatal Exposure Sensitizes for Zinc/Paraquat-Induced Neuronal Apoptosis, Adulthood Exposure Leads to the Final Effects - Namrata Mittra; Garima Singh; Chetna Singh (Journal of Molecular Neuroscience, 2026)

Etiology and co-infection patterns of acute respiratory viral infections in Bhopal, India: insights from short-term molecular study - Harjeet Singh Maan; Deepti Chaurasia; Lokendra Dave; Shweta Sharma; Mahendra Kumar Kumar; Savita Pal; Praveen Dandekar; Garima Kapoor (VirusDisease, 2026)

Quercetin Ameliorates Oxidative Stress, Inflammation and Metabolic Dysregulation in a D-Galactose-Induced Ageing Rat Model - Sakshi Jaiswal; Akanksha Singh; Garima Yadav; Nitin Mishra; Sandeep Yadav; Syed Ibrahim Rizvi (Indian Journal of Clinical Biochemistry, 2026)

Sources and characteristics of water and methanol soluble brown carbon over a megacity: Insights from EEM-PARAFAC approach - Swati Joshi; Atinderpal Singh; Chandrima Shaw; Garima Verma; Neeraj Rastogi (Environmental Pollution, 2026)

Interpenetrating polymer network microspheres based on alginate and thiolated CNF for tumor-triggered localized intratumoral therapy - Jomon George Joy; Garima Sharma; Fanyu Zhao; Jin-Chul Kim (Carbohydrate Polymers, 2026)

Quantification, Impacts, and Toxicity of Plastic Additive (Bisphenol A) at a Landfill Site: a Case Study of Jaipur City - Preksha Palsania; Charulata Sivodia; Garima Kaushik (Water, Air, & Soil Pollution, 2026)

Bioclimatic conditions on the Labrador Peninsula coast in 1884–1889, with a comparison to 1991–2020 at Nain station - Konrad Chmist; Andrzej Araźny; Rajmund Przybylak; Garima Singh; Przemysław Wyszyński (International Journal of Biometeorology, 2026)

KASP marker-assisted breeding for begomovirus-resistant pumpkin hybrids: resistance validation and heterosis for yield and horticultural traits - Anushka Sood; Madhu Sharma; Neha Verma; Garima Verma; Ajmer Singh Dhatt; Jiffinvir Singh Khosa; Abhishek Sharma; Om Prakash Meena (Horticulture, Environment, and Biotechnology, 2026)

Melanophore physiology and adrenergic receptor signaling in zebrafish (Danio rerio) - Sonakshi Gupta; Dileep Gupta; Mohd. Mubashshir; Garima Awasthi; Kumud Kant Awasthi (Fish Physiology and Biochemistry, 2026)

Dynamics of Chill Accumulation and Yield Performance of Selected Apple Cultivars in Mid-Hill Regions of Himachal Pradesh, India - Garima Vashisth; Sanjeev Kumar; Rupam Nehta; Pramod Verma; Ibajanai Kurbah; Nitin Sharma; Neena Chauhan (Applied Fruit Science, 2026)

Protective effects of gastrodin against bisphenol A-induced dopaminergic dysregulation and cognitive impairment in rats - Mohd. Anas Saifi; Mehjbeen Javed; Garima Jindal; Nidhi Agarwal; Sheikh Raisuddin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

From glycemic control to neuroprotection: alogliptin as a repurposed candidate for Huntington’s disease - Garima Choudhary; Kanika Vashisht; Varun Sharma; Mahendra Singh Ashawat; Shiv Kumar Kushawaha (Metabolic Brain Disease, 2026)

Chickpea ‘Seed Filling and Maturation’ (CaSFAM), a putative cytidine deaminase gene, can regulate key genes for seed development - Prashant Yadav; Asim Kumar Ghosh; Garima Chauhan; Sonali Paul; Swarup K. Parida; Kaustav Bandyopadhyay (Journal of Plant Biochemistry and Biotechnology, 2026)

Comprehensive genome-wide analysis of DUF668 gene family in potato reveals roles in growth and stress responses - Aiana Gill; Tanvi Mongia; Garima Kakkar; Santosh Kumar Upadhyay; Kashmir Singh (Journal of Applied Genetics, 2026)

Machine learning–guided discovery of spirocyclic inhibitors targeting Mycobacterium tuberculosis FtsZ - Rahul Singh; Vivek Dhar Dwivedi; Garima Chouhan (Folia Microbiologica, 2026)

Antifungal potential of B. amyloliquefaciens NBRI-SN13 against R. solani: Parallels and contrast with epigenetic modifier - Ananya Dwivedi; Akshita Maheshwari; Garima Saxena; Sushree Pallavi; Anamika Asthana; Sushmita; Babita Kumari; Mehar H. Asif; Suchi Srivastava (Process Safety and Environmental Protection, 2026)

Late-Holocene monsoon variability in the Purna Basin revealed from multiproxy study, Central India - B.V. Lakshmi; K. Deenadayalan; Garima Shukla; Priyanka Singh; Anupam Sharma; A.P. Dimri (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mitigating microplastic contamination in the food chain via microalgae: Sequestration and bioplastic production - Rohit Sharma; Priyvart Choudhary; Vinay Kumar Pandey; Garima Kumari; Shailendra Thapliyal; Gurmeet Singh; Gurpreet Kaur (Food Bioscience, 2026)

Spatiotemporal targeting of miR-125b-5p regulatory hub via dual-ligand nanocarriers to polarize tumor-associated macrophages towards tumoricidal phenotype in breast cancer microenvironment - Garima Sharma; Ashish Ranjan Sharma; Varun Dewaker; Songrae Kim; Hoibin Jeong; Jin-Chul Kim (Chemical Engineering Journal, 2026)

Small RNA sequencing unveils predominant expression patterns and miRNA-target modules associated with seed development in sorghum - Rubi Jain; Garima Yadav; Namrata Dhaka; Ira Vashisht; Anisha Maheshwari; Anisha Thalor; Manoj K. Sharma; Rita A. Sharma (Physiology and Molecular Biology of Plants, 2026)

Fly ash from Delhi municipal solid waste incineration facilities: identification of contaminants of concern for regulatory-informed management - Deepesh Bansal; Garima Gupta; G. V. Ramana; Manoj Datta; Kai Yao (Clean Technologies and Environmental Policy, 2026)

Rational design and synthesis of theophylline-based hybrids as bacterial DHFR inhibitors: integrating molecular modelling and ADME prediction with biological validation - Jyoti; Garima; Nitish Kumar; Megha; Karanvir Singh; Rupali Rana; Aanchal Khanna; Irvanpreet Kaur; Sumanpreet Kaur; Preet Mohinder Singh Bedi (In Silico Pharmacology, 2026)

Insights on molecular drivers of phenotypic plasticity in Candidozyma auris - Shivani Solanki; Bharti Singh; Kartavya Mathur; Shumaiza Asif; Ashik Francis; Garima Gangwar; Anil Thakur; Rekha Puria (World Journal of Microbiology and Biotechnology, 2026)

Predicting flavor perception from multisensory stimuli using machine learning: A neurogastronomic approach - Vikas Sharma; Garima Jain (International Journal of Gastronomy and Food Science, 2026)

Eco-friendly fabrication of La-doped ZrO2 nanoparticles using lentinula edodes extract for selective Hg2+ ion detection - Garima; Ashif Choudhary; Vivek Sheel (Environmental Nanotechnology, Monitoring & Management, 2026)

Advanced NanoBiochar approaches for heavy metal detoxification in rice, wheat agroecosystems and challenges - Garima Awasthi; Vaibhav Sharma; Nandini Chauhan; Mahipal Singh Sankhla; Anjali Awasthi; R.D. Tripathi; Sudhakar Srivastava; Shraddha Singh; Anuj Sharma; Kumud Kant Awasthi (Environmental Nanotechnology, Monitoring & Management, 2026)

Reproductive challenges in Indian dairy farming: an analysis of repeat breeding and infertility in Tamil Nadu - Thanammal Ravichandran; Garima Digdarshika; Mizeck G. G. Chagunda; Arunkumar Krishnamoorthy; P. Shanthra; Kiruthika Nallasamy; Chitra Ramasamy; Mohanamani Palanisamy (Tropical Animal Health and Production, 2026)

Identification and Characterization of NAC Transcription Factor-Based Simple Sequence Repeat Markers and Genome-Wide Association Studies for Seed Longevity in Alliums - Deepanshu Jayaswal; Deepesh Kumar; Nandita Banerjee; Ankit Badesra; Himanshu Sharma; Garima Yadav; Sanjay Kumar; Rajiv Baliram Kale; Kuldip Jayaswall (Plant Molecular Biology Reporter, 2026)

Developing an effective Agrobacterium-mediated transformation system for Bryophyllum pinnatum - Garima Sharma; Alka Jangra; Shalu Yadav; Siddharth Tiwari; Vinod Chhokar (Plant Cell, Tissue and Organ Culture (PCTOC), 2026)

From gastric to neuroprotection: pantoprazole mitigates epilepsy via TrkB/BDNF and KCC2 modulation - Arya Kuhu Vishwapriya; Kamini Verma; Garima Sharma; Nitika Sindhu; Swati Paliwal; Smita Jain; Jaya Dwivedi; Sarvesh Paliwal; Swapnil Sharma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Comprehensive Assessment of Prenatal Exposure to Endocrine Disrupting Chemicals: A Prospective Cohort Study on Indian Pregnant Women - Tarang Gupta; Chippy Anna Joy; Aishwarya Jala; Rajesh Khadgawat; Roshan M. Borkar; Garima Kachhawa; Ramu Adela (Exposure and Health, 2026)

Barley (Hordeum vulgare L.) malt quality: from historical practices to contemporary biotechnological advances - Shalu Yadav; Dinesh Kumar; Alka Jangra; Garima Sharma; Santosh Kumar Bishnoi; Ravinder Kumar; Anil Kumar; Vinod Chhokar (Cereal Research Communications, 2026)

Molecular, structural and functional characterization of flavonol synthase gene and its encoded protein in Millettia pinnata - Garima Kumari; Hemanti Kumari; Vinod Kumar Nigam; Dev Mani Pandey (Biotechnology Letters, 2026)

Geographic and botanical determinants of propolis: variability in chemical constituents and antimicrobial effects - Mukul Maurya; Garima Sahu; Md Sadique Hussain; Anas Islam; Bedanta Bhattacharjee; Shanti Bhushan Mishra; Sanjesh Kumar; Sathvik Belagodu Sridhar; Uttam Prasad Panigrahy; Anant Deogaonkar; Sabina Yasmin; Sumel Ashique; et al. (Plant Biosystems, 2026)

Smart agroforestry interventions for enhancing livelihood and ecological resilience in semi-arid regions - Prabhat Tiwari; Garima Gupta; Pankaj Lavania; Soumyajeet Sahu; Preeti Kumari; Manmohan Dobriyal; S. S. Singh; Manish Srivastav; A. K. Singh; Pavan Kumar (Agroforestry Systems, 2026)

Molecular Mechanisms of Herbal Drugs in Modulating Insulin Resistance: Focus on AMPK, PPARs, and mTOR Pathways - Prachi Goswami; Garima Mathur; Shivani Sharma; Devika Gautam; Kalpana Swain; Satyanarayan Pattnaik (Current Pharmacology Reports, 2026)

Changing patterns of evapotranspiration and its feedbacks on precipitation under a changing climate across India's homogeneous regions using GLDAS data - Garima Singh; Sudhir Kumar Singh (Journal of Atmospheric and Solar-Terrestrial Physics, 2026)

Bridging Artificial Intelligence, Machine Learning with Green Nanotechnology: A Visionary Framework for Smart Fungal Disease Management in Plants - Garima Yadav; Arti; Jyoti Mathur (Planta, 2026)

Integrative Genomic and Structural Analysis Reveals Diversity and Stability of yefM-yoeBXn Toxin-Antitoxin Module in Xenorhabdus nematophila - Garima Singh; Meenakshi Chaudhary; Nomita Gupta; Shobhi Chaudhary; Vikrant Nain; Jitendra Singh Rathore (Current Microbiology, 2026)

Phytochemical profiling and bioactive assessment of Crassocephalum crepidiodes using GC-MS and LC-MS analysis - B. C. Lalremruata; Nick Lalrinmawia; Garima Singh (Vegetos, 2026)

Production and characterization of polyhydroxyalkanoates by a novel strain Priestia flexa JP1 - Rakhi Pandey; Garima Mathur (Biologia, 2026)

The molecular network in bacteria responsible for the mitigation of salinity stress - Garima Alhan; Meena Sindhu; Ajay Kumar; Sushil Nagar; Suruchi Sangwan; Gulab Singh; Ram Prakash; Santosh Rajan Mohanty (World Journal of Microbiology and Biotechnology, 2026)

Cubosome-Based Nanocarriers in Cancer Therapy: Design Optimization, Analytical Characterization, and Translational Perspectives - Urushi Rehman; Syed Parween Ali; Umme Hani; Garima Gupta; Khang Wen Goh; Prashant Kesharwani (Annals of Biomedical Engineering, 2026)

A review of integrated pest management practices in high tunnel specialty crop production - Eleanor L. Meys; Samantha A. Willden; Laura L. Ingwell; Garima Kohli; Kacie J. Athey (Crop Protection, 2026)

Evidence for shock-induced transformation and incipient melting of pyroxene in impact-melt bomb from Lonar Impact Crater, India - Kishan Tiwari; Dwijesh Ray; Saumitra Misra; Garima Arora (Journal of Asian Earth Sciences, 2026)

Hydrodynamic Fate and High-Hazard Source Apportionment of Microplastics in Freshwater Bodies of Semi-Arid Rajasthan, India - Charulata Sivodia; Mohd Ashraf Dar; Milap Dashora; Ommer Ahad Bhat; Shailesh Kumar Patidar; Garima Kaushik (Water Conservation Science and Engineering, 2026)

Epigenomic Regulation Controls the Two-Component System Genes During Fruit Ripening - Yogeshwar Vikram Dhar; Ravi Shankar Kumar; Priyamvada Mishra; Garima Saxena; Vaishali Pankaj; Rayees Ahmad Lone; Prabodh Kumar Trivedi; Mehar Hasan Asif (Journal of Plant Growth Regulation, 2026)

Cloning and Heterologous Expression of a Novel Thermo-Alkalistable GH-10 Xylanase (rXyn-GM) Retrieved from Tapovan Hot-Spring Soil Metagenome and its Characterization for Kinetic Parameters - Garima Chauhan; Nivedita Bisht; Praveen Gautam; Meghna Arya; Asha Kumari; Digvijay Verma; Monica Sharma (Indian Journal of Microbiology, 2026)

Author Correction: Gonadal transdifferentiation in teleosts during normal and altered physiology—a review - Garima Vats; Keith B. Tierney; Balasubramanian Senthilkumaran (Fish Physiology and Biochemistry, 2026)

Ranking Barriers and Interventions for Circular Economy in Fashion: A Theory-Anchored Multi-Stakeholder Study - Garima Singh (Circular Economy and Sustainability, 2026)

Characterizing Biochemical Traits and Hormonal Profiling Linked to Stress Resilience in Apple Cultivars from the Mid-Hills of Himachal Pradesh, India - Garima; Sanjeev Kumar; Rupam Nehta; Pramod Verma; Ibajanai Kurbah; Vijit Gupta; Syed Mudassir Jeelani; Neena Chauhan (Applied Fruit Science, 2026)

Provenance, tectonic setting and paleoenvironment of the Tura Sandstone Formation, Northeast India: An integrated approach - Pradip Borgohain; Devojit Bezbaruah; Yadav Krishna Gogoi; Anurag Bharadwaj; Bishal Singh; Garima Konwar; Dipankar Saikia; Mondip Sarma; Bubul Bharali (Acta Geochimica, 2026)

Bisphenol S and F disrupt cerebellar functions and neuronal health: The role of estrogen receptor and BMP2 signaling - Uttara Das; Neetu Shukla; Deeksha Ojha; Garima Sagar; Somendu Kumar Roy; Sanghamitra Bandyopadhyay (Toxicology Letters, 2026)

Multilevel evaluation of Hyptis suaveolens essential oil against papaya postharvest fungal pathogens: in vitro, mechanistic and in vivo evidence - Priyankaraj Sonigra; Garima Yadav; Adhishree Nagda; Tushar Mehta; Mukesh Meena; Abhishek Sahoo (Food Chemistry, 2026)

Concurrent endoplasmic reticulum stress and demyelination in DEHP-exposed zebrafish larvae at the early developmental stages - Garima Jindal; Anuradha Mangla; Mehjbeen Javed; Mohd. Anas Saifi; Iqra Mazahir; Padmshree Mudgal; Shiekh Raisuddin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Waste to wealth: sustainable approach of alchemizing mushroom SMS into bioenergy - Garima Gupta; Sandhya Maurya; Durgesh Singh (Bioresource Technology, 2026)

Long-term seasonal variability in the water-soluble inorganic composition of coarse and fine aerosols over the northeast Arabian sea - Garima Shukla; Ashwini Kumar; Ankush Kaushik (Atmospheric Pollution Research, 2026)

Carcinogenic and non-carcinogenic health risk assessment of river Ganges in different climatic conditions and regions of Uttarakhand, India - Prashant Kumar; Ashish Kothari; Shashi Ranjan Mani Yadav; Sandeep Kumar; Anindita Mandal; Garima Mamgain; Balram Ji Omar; Ajeet Singh Bhadoria; Bhupender Singh; Ankur Kumar; Anissa Atif Mirza (The Nucleus, 2026)

Comparative study of bioclimatic conditions in southwestern Greenland between the late 18th century and the present - Andrzej Araźny; Konrad Chmist; Rajmund Przybylak; Przemysław Wyszyński; Garima Singh (International Journal of Biometeorology, 2026)
The paper compares the scope and nature of changes in meteorological and biometeorological conditions in Nuuk (SW Greenland) in the second half of the 18th century for “expedition years” (Sep–Aug of: 1767–68, 1789–90, 1790–91 and 1791–92) against the contemporary period (1991–2020). The analysis used air temperature, wind speed and biometeorological indices: wind chill temperature (WCT) and insulation predicted (Iclp). The analysis was performed for individual days and months, and the comparison covers mainly the period January–June, for which complete data are available. The study showed that, in the years 1789–92, the prevailing conditions according to WCT were very similar to the contemporary period. However, according to WCT, 1768 was 4.5 °C milder for humans compared to current prevailing conditions for the period January–June. These relationships are also confirmed by the analysis of the Iclp index. Weather conditions were decidedly less burdensome for humans in 1768; for example, a person on the move needed about 0.3 clo less clothing than today. This paper is the first historical bioclimatology study of weather conditions for humans in 18th-century Greenland.

DPPH Rf-shift assay to overcome spectral interference: A rapid, portable TLC-based approach for semi-quantitative antioxidant evaluation - Garima Singh; Perinkulam Ravi Deepa; Prabhat Nath Jha (Analytica Chimica Acta, 2026)

Bioremediation of oil contaminants from the marine ecosystem by Alcanivorax borkumensis: an overview - Swati Sharma; Garima Sachan; Shreya Gupta; Shikha Chauhan; Saptak Sarkar (Archives of Microbiology, 2026)

Agroforestry for climate action: spatial extent and carbon sequestration potential in Kangra District of North-western Himalayas - Prashant Sharma; Daulat Ram Bhardwaj; Kamlesh Verma; Manoj Kumar Singh; Garima Gupta; Pankaj Thakur; Dhirender Kumar; Vaishali Sharma (Agroforestry Systems, 2026)

Histone modifications in biological age determination: mechanisms, biomarkers, and therapeutic perspectives - Anjali Tripathi; Garima Sharma; Vinay Kumar Pandey; Sarvesh Rustagi; Ashish Ranjan Sharma; Meenakshi Jha; Abhijit Debnath; Jomon George Joy; Jin-Chul Kim; Abhimanyu Kumar Jha (GeroScience, 2026)

Picophytoplankton biogeography, community structure, and carbon biomass in the Eastern Indian Ocean during the spring inter-monsoon season - Garima Chaudhari; Smita Mitbavkar; Pranoy Paul; Jagadish S. Patil; Samir Damare (Progress in Oceanography, 2026)

Unraveling the potential of soil microorganisms for nutrient solubilization and simultaneous pesticide degradation toward sustainable agriculture - Shalni SATYA; Milap DASHORA; Preksha PALSANIA; Mohd Ashraf DAR; Garima KAUSHIK (Pedosphere, 2026)

Microplastic exposure and its impact on the growth and physiological functions of Cicer arietinum - Garima Kaushik; P. Manuraj; Mohd Ashraf Dar; Preksha Palsania; Shalni Satya; Ommer Ahad Bhat; Shailesh Kumar Patidar (Biocatalysis and Agricultural Biotechnology, 2026)

Dose-dependent phytotoxic effects of biosynthesized ZnO nanoparticles from Saraca asoca on rice seedlings: oxidative stress and growth inhibition - Ruhani Sharma; Ankush Agrawal; Sanjay Kumar; Manoj Kumar Sharma; Pankaj Nagar; Kamlendra Awasthi; Anjali Awasthi; Garima Awasthi; Kumud Kant Awasthi (Physiology and Molecular Biology of Plants, 2026)

Gonadal transdifferentiation in teleosts during normal and altered physiology—a review - Garima Vats; Keith B. Tierney; Balasubramanian Senthilkumaran (Fish Physiology and Biochemistry, 2026)

Synergistic Application of Nano-micro and Macronutrients in Wheat Alleviated Drought Stress with Enhanced Physiological Response and Anti-oxidant Enzyme Activity - Garima Chauhan; Anil Kumar; Tarun Sharma; Akashdeep Singh; Bharat Bhushan Rana; Sandeep Manuja (Journal of Plant Growth Regulation, 2026)

Remediation of hazardous explosive-contaminated soil at field scale: a data-oriented review of technologies, challenges and recommendations - Garima Upreti; S. Mary Celin; Krishank Yadav; Anil K. Haritash; Dipti Barui Bose; Arvind Kumar (Environmental Monitoring and Assessment, 2026)

Microplastic accumulation in marine organisms across trophic levels along the west coast of India - Monali Vasant Patre; Garima Bora; Sharayu Jakhete; Shawn Dsouza; Kartik Shanker (Marine Pollution Bulletin, 2026)

Formulation and development of thymoquinone-loaded ufasome hydrogel for effective treatment of onychomycosis - Mohd Shoab Ali; Urushi Rehman; Garima Gupta; Abdulrhman Alsayari; Shadma Wahab; Khang Wen Goh; Prashant Kesharwani (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Alpha Lipoic Acid Mitigates TBI-Induced Neuroinflammation by Regulating S100B/STIM Signaling via NF-ƙB Pathway - Iqra Mazahir; Bushra Wali; Ahmed Shaney Rehman; Gaurav Deep; Anuradha Mangla; Garima Jindal; Huma Khan; Suhel Parvez; Sheikh Raisuddin (Molecular Neurobiology, 2026)

Phyllosphere microbiome-mediated plant defense: from natural biocontrol to integrated pest management - Pankaj Kumar; Aditya Pathak; Himanshu Kumar; Garima Sharma; Prashant Mishra; Mahesh Kumar Bharti; Kamal Khilari (Symbiosis, 2026)

Farm-level adaptations to harvest logistics constraints in export-oriented grain systems - Garima; Doina Olaru; Brett Smith; Kadambot H.M. Siddique (Agricultural Systems, 2026)

Sonic Serenity: Piezoelectric Nanomaterials Reshaping Wound Healing Paradigms - Jyoti Chandra; Garima Gupta; Khang Wen Goh; Prashant Kesharwani (Annals of Biomedical Engineering, 2026)

Correction to: Xenobiotic Binding Domain of Glutathione S-Transferase Has Cryptic Antimicrobial Peptides - Soyar Horam; Sneha Raj; Vikash Chandra Tripathi; Garima Pant; Mitra Kalyan; Thota Jagadeshwar Reddy; Jesu Arockiaraj; Mukesh Pasupuleti (International Journal of Peptide Research and Therapeutics, 2025)

Challenges and Gaps in Understanding and Monitoring Low-Latitude F-region Plasma Irregularities - Astrid Maute; Tibor Durgonics; Joe Huba; Rayan Imam; Hanli Liu; Garima Malhotra; John Retterer; Claudia C. Stephan; Claudia Stolle; Endawoke Yizengaw (Surveys in Geophysics, 2025)

Comprehensive genome-wide study of Glutaredoxin (GRX) gene family in the liverwort Marchantia polymorpha and exploring their roles in abiotic stress tolerance - Shivani Singh; Garima Saxena; Prachi Mishra; Monica Kumari; Prasanna Dutta; Mehar Hasan Asif; Debasis Chakrabarty (Plant Gene, 2025)

In-situ hydrogen bonding driven green extraction of five Sudan dyes from tomato ketchup using thymol followed by UHPLC-PDA analysis - Alok Kumar; Ajay Kumar Pandey; Garima Sagar; Sana Bano; Somendu Kumar Roy (Food Chemistry, 2025)

Bioremediation of two persistent pesticides in biomixtures: Role of pre-exposed soils, biochar and bioaugmentation - Garima Sethi; Dhruba Marak; Renu Saini; Tirthankar Banerjee; Rajesh Kumar; Neera Singh (Bioresource Technology Reports, 2025)

Development of solenoidal assembly for probing static magnetic field-induced physiological and behavioral disruptions in zebrafish - Anjani Dhayal; Srabaita Roy; Saidul Sk; Garima Jindal; Saran Kumar; Padmshree Mudgal; Rajesh Ramachandran; Marshal Dhayal; Shilpi Minocha (Aquatic Toxicology, 2025)

Combined Application of Pressmud-derived Biochar and PGPR Enhances Agronomic and Biochemical Traits of Strawberry (Fragaria × ananassa var. Camarosa) - Mohamed T. Ahmed; Sulaiman A. Alrumman; Garima Kumari; Sami Abou Fayssal; Ivan Širić; Pankaj Kumar; Madhumita Goala (Water, Air, & Soil Pollution, 2025)

Physiological, Biochemical, and Molecular Responses During Grafting in Horticultural Crops - Narayan Lal; Vikas Ramteke; Garima Diwan; Pragya Singh; Nisha Sahu; Debashish Hota; Maneesha S.R.; Nirmal Kumar Meena; Kapil Mohan Sharma; Govind Balasaheb Shiurkar; Ganesh Maske; N. R. Rangare (Plant Molecular Biology Reporter, 2025)

Keeping an eye on climate change? Effects on vision health - Garima Singh; Divya Singh; Barry T Rouse; Pranita P Sarangi (Journal of Biosciences, 2025)

Lactoferrin-modified PLGA nanoparticles for pregabalin: development, characterization, in vitro targeting and pharmacodynamic evaluation - Garima Rai; Pammi Gauba; Amit Tyagi; Shweta Dang (Drug Delivery and Translational Research, 2025)

Identifying the Degree of Gene Reuse During Repeated Adaptation - Samridhi Chaturvedi; Lakshmi Vineesha Digumarthi; Garima Setia (Molecular Ecology, 2025)
The degree or extent of gene reuse during repeated adaptation offers key insights into the genomic constraints on evolution. Although many studies have identified signs of genomic repeatability, a thorough synthesis of methods for detecting gene reuse and estimating its extent is missing. In this review, we first propose a simple framework for studies aimed at identifying gene reuse during repeated adaptation using genomic data. Next, we examine existing approaches to (i) detect gene set overlap, perform significance testing, and perform multivariate dimensionality reduction, (ii) distinguish between gene and allele reuse while emphasising methods for detecting allele reuse, (iii) explore models to identify the mechanisms behind repeated adaptation, and (iv) address issues and potential solutions to differentiate true gene reuse from methodological artifacts. Our review highlights standardised methods developed using genomic data to identify gene reuse. We also note that, although few studies quantify allele reuse, conducting such analyses is essential because it adds a more detailed layer to predicting evolutionary paths. Finally, several strategies can be used to cross‐validate signals of gene reuse. These should be applied to confirm true positives, as biological and methodological artifacts can bias predictions. By synthesizing current methods and outlining a robust analytical framework, we provide a roadmap for enhancing the accuracy and reliability of gene reuse detection in adaptive evolution.

Chemical composition of aerosols over the Bay of Bengal based on global reanalyses data and on-board ship measurements - Garima Shukla; Ashwini Kumar (International Journal of Remote Sensing, 2025)

Recent advances in phosphorus nano-fertilizers: Impacts on crop productivity and soil sustainability - Vivek Kumar Dhiman; Vinay Kumar Dhiman; Garima Rana; Rakesh Kumar; Devendra Singh; Ankush Chauhan; Majid Jabir; Suresh Ghotekar (Physiological and Molecular Plant Pathology, 2025)

Meta-analysis of metabolic responses of earthworms to Agrochemicals: Dose-Response, temporal trends, and pathway perturbations - Praddum Kumar Namdev; Garima Stephen; Shweta Yadav (Environmental Pollution, 2025)

Analyzing and predicting ventilation coefficient over India using long-term reanalysis datasets and hybrid machine learning approach - Amitabha Govande; Raju Attada; Krishna Kumar Shukla; Soumya Muralidharan; Ravi Kumar Kunchala; Nagaraju Chilukoti; Garima Kaushik (Theoretical and Applied Climatology, 2025)

Cannabichromene, a key non-psychotropic phytocannabinoid in treatment of major depressive disorder: in silico and in vivo explorations - Abhishek Sharma; Rahul Singh; Tarun Virmani; Neeraj Kumar Chouhan; Garima Kapoor; Girish Kumar; Rubina Bhutani; Neha Rana; Shivkant Sharma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Differential Assembly of Core and Non‐Core Host‐Microbe Network Structures Along a Land‐Use Change Gradient - Matan Markfeld; Georgia Titcomb; Toky Maheriniaina Randriamoria; Garima Sehgal; Nuzha Baksh; Ashley Kerrigan; Voahangy Soarimalala; Charles L. Nunn; Shai Pilosof (Ecology Letters, 2025)
Microbial communities are fundamental to host health, yet their assembly dynamics under environmental change remain poorly understood. We analysed individual‐level host‐microbe networks in the non‐native wild black rats ( Rattus rattus ) across a land‐use gradient in Madagascar. By applying a moving prevalence threshold, we distinguished between core and non‐core microbes and compared the assembly drivers shaping their network structures. Non‐core microbes formed fragmented, modular networks shaped mainly by heterogeneous selection, reflecting environmental filtering. In contrast, core microbes exhibited stable, less modular networks driven primarily by stochastic ecological drift. These distinct assembly processes persisted across thresholds, highlighting fundamental differences in microbial structuring. Land‐use change significantly influenced the modular structure of non‐core microbes but had minimal effects on core microbes, demonstrating the differential sensitivity of microbial groups to environmental variation. This study advances our understanding of host–microbe interactions and provides a framework for assessing microbiome assembly under anthropogenic change.

Effect of tricyclazole aging in soils on its uptake in rice seedlings - Renu Saini; Garima Sethi; Dhruba Marak; Tirthankar Banerjee; Rajesh Kumar; Neera Singh (Environmental Monitoring and Assessment, 2025)

Usnic acid enantiomers in the lichen-forming fungal family Parmeliaceae - Maonian Xu; Garima Singh; Starri Heidmarsson; Elín S. Ólafsdóttir (Phytochemistry Letters, 2025)

Developmental and neurobehavioral toxicity of di-(2-ethylhexyl) phthalate (DEHP) in zebrafish larvae - Garima Jindal; Anuradha Mangla; Poonam Goswami; Mehjbeen Javed; Mohd. Anas Saifi; Iqra Mazahir; Padmshree Mudgal; Basir Ahmad; Sheikh Raisuddin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Unlocking the Power of Xylooligosaccharides as Nutraceuticals: Sources, Production Strategies, and Applications - Anupama Sharma; Garima Dulgach; Rahul Warmoota; Kumud Sharma; Aditya Kumar; Phalguni Gupta; Naveen Gupta (Sugar Tech, 2025)

Geochemical assessment of heavy metals and Pb isotopic characterization of soils of automobile garage areas in Chandigarh, India - Garima Kumari; Avijit Das; Subhra Sarita Patel; Rajeev Kumar (Arabian Journal of Geosciences, 2025)

Nanopesticides in plant protection: Potentials, mechanistic insights, and future perspectives against phytopathogens and insect pests - Garima Bhanwala; Neetika Kimta; Karthikeyan Ravi (Physiological and Molecular Plant Pathology, 2025)

Nanomaterials for sustainable agriculture: Plant physiology and environmental resilience - Vivek Kumar Dhiman; Garima Rana; Vinay Kumar Dhiman; Rajasekaran Subbarayan; Mukul Sharma; Devendra Singh; Majid Jabir; Suresh Ghotekar; Ankush Chauhan (Physiological and Molecular Plant Pathology, 2025)

Enhancing antibiotic potency with Adiantum venustum D. Don extracts and fractions: A phyto-antibiotic synergistic approach against microbial strains - Neetika Kimta; Garima Bhanwala; Sunil Puri (Next Research, 2025)

A comprehensive overview of AI–nanotech convergence for a resilient future - Mohd. Aslam; Anjali Rani; Javed Khan; Shreshth Pandey; Bhaskara Nand; Prashant Singh; Garima Pandey (Next Research, 2025)

Transforming agricultural biomass into lead-free X-ray shielding and efficient photocatalytic material based on 2D-MoS2/TiO2 nanocomposite - Noona Shahada Kunnath Parambil; Selwin Joseyphus Raphael; Thanigainathan Prakash; Pushparajan Joseph; Garima Thakur; Arish Dasan (Bioresource Technology Reports, 2025)

Microbial degradation of textile dye reactive blue 250 (RB 250) by the novel Pseudomonas aeruginosa RGB11: a sustainable approach - Garima Chetry; Vasantha Veerappa Lakshmaiah (Brazilian Journal of Microbiology, 2025)

Mechanistic inhibition of FtsZ-driven bacterial cytokinesis by natural products: an integrated machine learning and advanced drug discovery approach - Rahul Singh; Vishwas Tripathi; Vivek Dhar Dwivedi; Garima Chouhan (Molecular Diversity, 2025)

Intention to action: A theory of planned behavior (TPB) approach to understand college students’ control over binge-watching - Garima Sainger (The Social Science Journal, 2025)

Growth, yield and quality of sprouting broccoli (Brassica oleracea L. var. italica) as influenced by different mulches - Garima Kumari; Monisha Rawat; Khushboo Kathayat (Vegetos, 2025)

Advanced water treatment with antimicrobial silver-lignin nanoparticles sonochemically-grafted on cork granulates in activated carbon packed-bed columns - Jeniffer Blair; Garima Rathee; Antonio Puertas-Segura; Leonardo Martín Pérez; Tzanko Tzanov (Environmental Research, 2025)

Life cycle assessment of Jatropha and rapeseed biodiesels: Cradle to grave - Sophie Shrees; Ayesha Masood; Yutshu Shrestha; Garima Garima (Biomass and Bioenergy, 2025)

S292L mutation in Rv1258c efflux pump drives pyrazinamide efflux and a novel inhibitor designed for co-therapy to improve MDR-TB treatment outcomes - Garima Singh; Shriti Shreya; Saurabh Yadav; Yusuf Akhter (World Journal of Microbiology and Biotechnology, 2025)

Speed-bred crops for food security and sustainable agriculture - Garima Aggarwal; A. S. Jeena; Kajal Mehra; Bishawajit Kumar; Shivani Kashyap; Dhananjay Kumar Yadav; Alok Kumar Maurya; S. C. Venkatesh; Prakhar Singla; Abhishek Bohra (Planta, 2025)

Artificial light at night accelerates aging processes in pre-pubertal female rats - Garima Yadav; Akanksha Singh; Amit Kumar Trivedi; Syed Ibrahim Rizvi (Biogerontology, 2025)

Petrographic and geochemical perspectives on sandstones of the extra-peninsular Gondwana Group from the Arunachal Himalayas, NE India: Probing provenance, tectonic context and paleoenvironmental conditions - Yadav Krishna Gogoi; Pradip Borgohain; Diganta Bhuyan; Devojit Bezbaruah; Garima Konwar; Manash Pratim Gogoi; Bubul Bharali (Acta Geochimica, 2025)

Gallic Acid-Loaded Transethosomal Gel for Enhanced Topical Delivery and Sustained Therapeutic Efficacy in Psoriasis Management: Formulation, Optimization, In Vitro and Ex Vivo Assessment - Tenzin Sonam Dongsar; Tenzin Tsering Dongsar; Abdulrhman Alsayari; Shadma Wahab; Garima Gupta; Prashant Kesharwani (AAPS PharmSciTech, 2025)

Stacking of elite indica rice genotype with bacterial blight, blast, and Brown plant hopper resistance genes through marker assisted selection - Velprabakaran Senthilvel; Garima Pelhania; Gokulakrishnan Moorthy; Yazhini Sukumar; Priyanka Ariyapalayam Rajendran; Suji Kalampalayam Krishnaswamy; Chudamani Sridhar; Harsa pravena Viswanathan; Swetha Dhamodaran; Thirumalraj Samikannu; Sravanthi Ragulakollu; Bonipas Antony John; et al. (Physiological and Molecular Plant Pathology, 2025)

Shifting Patterns in the Weather Regimes That Drive Regional Drought: Demonstration for South Africa - Garima Mandavya; Gaurav Atreya; John Kucharski; Andrew Watson; Nasser Najibi; Koen Verbist; Patrick Ray (International Journal of Climatology, 2025)
Traditional vulnerability assessments of climate change impacts often rely on randomised precipitation scenarios that lack a strong physical science basis. Furthermore, the limitations of General Circulation Models (GCMs) in accurately representing local precipitation fields undermine their utility for projecting future hydroclimatic extremes. To address these gaps in climate risk management, this study explores the role of large‐scale atmospheric circulation patterns, known as weather regimes (WRs), in explaining local and regional precipitation dynamics in South Africa. Utilising a Non‐Homogeneous Hidden Markov Chain approach, we identified six primary WRs for South Africa, each exhibiting distinct seasonal patterns. The results show that winter precipitation near Cape Town is dominated by three WRs linked to higher rainfall, whilst summer precipitation is influenced by two WRs associated with drier conditions. The WR‐precipitation relationship in South Africa appears to be influenced by topographic features (e.g., The Great Escarpment and Cape Fold Mountains) and ocean currents (Agulhas and Benguela), leading to distinct spatial precipitation responses to regional WR configurations. Importantly, significant shifts in seasonal WR frequencies have been observed over the past two decades, particularly a marked change since 2010. Notably, a WR historically associated with rainfall in Cape Town has been replaced by a drier WR, contributing to worsening drought conditions, including the 2015–2017 “Day Zero” drought. During this period, the WR associated with dryness in Cape Town occurred more frequently than the historical average, whilst wetter years before and after the drought were characterised by low‐pressure (low 500 hPa geopotential height anomalies) WRs conducive to precipitation. In contrast, the drought years were dominated by high‐pressure (high 500 hPa geopotential height anomaly) WRs associated with dry conditions. This WR‐precipitation analysis underscores the critical link between atmospheric circulation patterns and regional hydroclimatic extremes. These findings can inform the development of WR‐based rainfall generators, providing valuable tools for vulnerability assessments and climate change adaptation planning.

Deciphering the multifaceted mechanism of Trichoderma asperellum ORF 2 parasitism against Alternaria porri in confronting onion purple blotch - Shubham Saini; Hemant Kumar; Leela Wati; Rakesh Kumar; Anil Kumar Saini; Shweta; Ankit Saini; Garima; Kalpana Yadav; Kushal Raj (Journal of Plant Pathology, 2025)

Decreasing farm sizes and the viability of smallholder farmers: Implications for resilient and inclusive rural transformation - Sarah K. Lowder; Garima Bhalla; Benjamin Davis (Global Food Security, 2025)

A review on accessible techniques for the management of rice false smut: recent research and future outlook - Prasenjit Debnath; Sonam Mahawar; Garima Singh (Planta, 2025)

The native Indian mimosoid tree Prosopis cineraria shares diverse root nodulating rhizobia symbionts with exotic species of Neltuma (ex-Prosopis) - Garima Bissa; Nisha Tak; Bhawana Chouhan; Euan K. James; Hukam S. Gehlot (Plant and Soil, 2025)

“Methyl jasmonate: bridging plant defense mechanisms and human therapeutics” - Garima Sharma; Badruddeen; Juber Akhtar; Mohammad Irfan Khan; Mohammad Ahmad; Prakash Kumar Sharma (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Characterizing trait-specific populations and genetic diversity patterns in clary sage (Salvia sclarea L.) using SSR markers - Niketa Yadav; Mohar Singh; Asmita Saini; Pratibha Pandey; Garima Thakur; Ramesh Chauhan; Satbeer Singh; Sanatsujat Singh (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

Advances in using non-thermal plasmas for healthier crop production: toward pesticide and chemical fertilizer-free agriculture - Priti Pal; Hansa Sehgal; Mukul Joshi; Garima Arora; Milan Simek; Ram Prakash Lamba; Shivendra Maurya; Udit Narayan Pal (Planta, 2025)

Global genecological status of vulnerable Dalbergia latifolia: need to introspect the conservation perspectives - Maneesh S. Bhandari; Shailesh Pandey; Rama Kant; Pooja Joshi; Garima Thapliyal; Garima Mishra; Tushal Srivastava; Rajendra K. Meena; Surendra S. Bisht (Vegetos, 2025)

Wellness tourism: nurturing nature and achieving sustainable development goals (SDGs) while travelling - Kaushik Nagadev Bhuyan; Rajashree Naik; Garima Khangarot (Environment, Development and Sustainability, 2025)

Chemical composition of aerosols over the Arabian Sea based on global reanalyses data and on-board ship measurements - Garima Shukla; N. Ojha; Ashwini Kumar; S. Harithasree; I. Girach; L.K. Sahu (Atmospheric Environment, 2025)

Seasonal dynamics and enzyme profiles of diverse endophytic fungi in Sterculia urens Roxb.: insights into host-associated trends - Garima Yadav; Mukesh Meena (World Journal of Microbiology and Biotechnology, 2025)

Artificial Intelligence: Preface, Applications and Future Perspective in Relation to Pharmaceutical Sector - Supriya Singh; Sanket Kumar; Sheikh Shahnawaz Quadir; Saloni Bhandari; Bhuvanesh Baniya; Garima Joshi; C. P. Jain; Deepak Choudhary (Journal of Pharmaceutical Innovation, 2025)

Growth-Promoting Endophytes as Immunity Booster for Brassica juncea against Insect Attack - Kavita Verma; Surbhi Agarwal; Garima Sharma; Apeksha Singhal; Richa Mullick; Vartika Mathur (Journal of Chemical Ecology, 2025)

Exploration of novel phytochemicals as α-synuclein aggregation inhibitors in the context of Parkinson’s disease therapy: an in-silico approach - Garima Gupta; Deepika Joshi; Gopeshwar Narayan; Sameer Sharma (In Silico Pharmacology, 2025)

Unraveling adaptive resilience, tolerance mechanisms, and mitigation potential of roadside tree species to vehicular emissions across urban habitats - Apurva Malik; Hukum Singh; Garima Kumari; Kishan Kumar; Sachin Shah; Santan Barthwal (Chemosphere, 2025)

Assessing the impact of microplastics on gonadal health of the spadenose shark (Scoliodon laticaudus) on the west coast of India - Haradhan Ruidas; Garima Bora; Shawn Dsouza; Kartik Shanker (Marine Pollution Bulletin, 2025)

Nanomaterials impact in phytohormone signaling networks of plants − A critical review - Garima Tripathi; Shrestha Dutta; Anamika Mishra; Soumyadeep Basu; Vishesh Gupta; Chinnaperumal Kamaraj (Plant Science, 2025)

The role of social protection in achieving resilient and inclusive rural transformation - Mari Kangasniemi; Garima Bhalla; Marco Knowles; Karen Codazzi Pereira; Ugo Gentilini (Global Food Security, 2025)

Hydrochemical Evaluation of Groundwater Quality and Human Health Risk Assessment of Fluoride and Nitrate: A Case Study of Pratapgarh District UP, India - Sandhya Maurya; Ashok B. More; Garima Gupta; Abhishek Saxena; Anjali Singh (Water, Air, & Soil Pollution, 2025)

Seed Priming with Fruit and Vegetable Waste-based Nanoparticles: A Sustainable Green Approach - Garima Yadav; Jyoti Mathur (Journal of Soil Science and Plant Nutrition, 2025)

A Comparative Study of Graphynes for Sensing of Gasses (SO2 & Acetylene) Using DFT Calculations and MD Simulations - Madhur Babu Singh; Garima Narang; Prashant Singh (Indian Journal of Microbiology, 2025)

Identification of Ecological Hotspots Using the Eco-track: Case of Keoladeo National Park, Bharatpur, India - Garima Toor; Neha Goyal Tater; Tarush Chandra (Environmental Management, 2025)

Changes in bioclimatic conditions on the coast of the Labrador Peninsula in the second half of the 18th century - Konrad Chmist; Andrzej Araźny; Rajmund Przybylak; Przemysław Wyszyński; Garima Singh (Climatic Change, 2025)
The article presents the bioclimate of the north-eastern part of the Labrador Peninsula estimated based on meteorological observations from three measuring stations: Nain, Okak and Hopedale. The meteorological measurements were taken by members of the Moravian Church conducting religious missions in the area. Two-time slots were designated: from September 1776 to August 1786, for which data exist for Nain and Okak stations; from September 1782 to August 1786 (with a year-long gap from September 1784 to August 1785), for which data exist for all three stations (Nain, Okak and Hopedale). The following indices were used: Wind Chill Temperature (WCT), Wind Chill Index (WCI) and Insulation Predicted (Iclp). The results were compared with the bioclimatic conditions in Nain from the contemporary period (1991–2000). It was found that, in the first of the specified time intervals (lasting 10 years), bioclimatic conditions were less bearable for humans in Nain than in Okak (for Nain and Okak the index values were as follows: WCT ˗0.8 °C and ˗0.4 °C, WCI 874.1 W∙m ˗2 and 802.2 W∙m ˗2 , Iclp equal 1.7 clo). In the second time period (only 3 years), the most difficult conditions prevailed at the Okak station while the most favourable were recorded at Hopedale (for Nain, Okak and Hopedale the index values were as follows: WCT ˗1.0 °C, ˗1.4 °C and 0.5 °C, WCI 881.6 W∙m ˗2 , 838.4 W∙m ˗2 and 819.6 W∙m ˗2 , Iclp 1.7 clo, 1.8 clo and 1.7 clo). At each station, conditions for humans were more favourable during the historical periods than in the contemporary period (WCT ˗2.7 °C, WCI 987.9 W∙m ˗2 , Iclp 1.9 clo). The most important role in this matter was played by wind speed, which was higher in 1991–2000 than in the second half of the 18th century.

Impaired Mitochondrial Function and Ubiquitin Proteasome System Activate α-Synuclein Aggregation in Zinc-Induced Neurotoxicity: Effect of Antioxidants - Garima Singh; Namrata Mittra; Chetna Singh (Journal of Molecular Neuroscience, 2025)

Tagitinin C- A potential anticancer agent from Tithonia diversifolia: A comprehensive review - B.C. Lalremruata; P.C. Vanlalhluna; Garima Singh (South African Journal of Botany, 2025)

Reducing silica in zirconium leachate from washed and dried frit powder: Role of cold and concentrated nitric acid and avoidance of crud formation - Sandeep Singh Tomar; Garima Pandey; Nirvik Sen; Gaurav Varshney; Sulekha Mukhopadhyay (Hydrometallurgy, 2025)

Metabolomics approach to evaluate diclazuril-induced developmental toxicity in zebrafish embryo - Veena Jain; Ved Prakash; Garima Sagar; Alok Kumar; Pankaj Ramji Jagdale; Anjaneya Ayanur; Sadasivam Anbumani; Somendu Kumar Roy (Aquatic Toxicology, 2025)

Molecular identification and elimination of endophytic contamination using antibiotics from in vitro culture of Vitex peduncularis Wall. Ex Schauer - Runam Kumari; V. Rathna; Garima Kumari; Animesh Sinha; Yogeshwar Mishra (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Comprehensive in-silico characterization and expression pattern of calmodulin genes under various abiotic and biotic stresses in Indian mustard (Brassica juncea) - Prashasti Pandey; Garima Rai; Anchal Garg; Deepak Kumar (Physiology and Molecular Biology of Plants, 2025)

Microplastic pollution: A global perspective in surface waters, microbial degradation, and corresponding mechanism - Mohd Ashraf Dar; Preksha Palsania; Shalni Satya; Milap Dashora; Ommer Ahad Bhat; Sana Parveen; Shailesh Kumar Patidar; Garima Kaushik (Marine Pollution Bulletin, 2025)

Bisphenol A-induced polycystic ovary syndrome (PCOS) with hormonal and metabolic implications in rats - Mehjbeen Javed; Suramya; Anuradha Mangla; Garima Jindal; Humaira Naaz Bhutto; Shaesta Shahid; Suraj Kumar; Sheikh Raisuddin (Reproductive Toxicology, 2025)

Phenotypic and molecular characterization of vernalization sensitivity and pre-mature bolting in onion (Allium cepa L.) - Garima Verma; Jiffinvir Khosa; M. Sharma; O. P. Meena; A. S. Dhatt (Genetic Resources and Crop Evolution, 2025)

Silent risk: the vertical transmission of Oropouche virus - Kukreja Garima S; Khopkar-Kale Priyanka S; Tripathy Srikanth P; Bhawalkar Jitendra S (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Potential Effect of Extracellular Vesicles in Clinical Settings of Lymphoma - Garima Mamgain; Shashi Ranjan Mani Yadav (Indian Journal of Clinical Biochemistry, 2025)

Late-stage Deccan eruption from multiple shallow magma chambers through vertical flow along fissures: Insights from magnetic fabric analysis of the Pachmarhi dyke swarm - Garima Shukla; Jyotirmoy Mallik; Yadav Krishna; Sayandeep Banerjee (Physics of the Earth and Planetary Interiors, 2024)

Recent advances in photothermal assisted photocatalytic CO2 reduction and H2 production by semiconductor heterojunctions - Pankaj Sharma; Amit Kumar; Tongtong Wang; Pooja Dhiman; Gaurav Sharma; Garima Rana (Journal of Environmental Chemical Engineering, 2024)

Identifying Bacteria from Urban Soil for Degrading Soil Organic Contaminants of Emerging Concern - Kavita Verma; Garima Sharma; Pooja Gokhale Sinha; Nishu; Vartika Mathur (Water, Air, & Soil Pollution, 2024)

Phenological pattern, breeding behaviour, and estimation of outcrossing rate in Grevillea robusta (Proteaceae) - Maneesh S. Bhandari; Aman Dabral; Anchal Bisht; Garima Mishra; Rajendra K. Meena; Rama Kant; Shailesh Pandey; Raman Nautiyal; Atika Chandra; Rajesh Tandon (The Nucleus, 2024)

Exploring miR-155-5p and miR-1246 as Diagnostic and Prognostic Markers in Oral Squamous cell carcinoma - R. Maheswari; Aadithya B. Urs; Priya Kumar; B. C. Koner; Sameer Ahmad Guru; Garima Rawat (Molecular Biology Reports, 2024)

Molecular Evidence of Crosstalk Between Bacterial Endophytes and Plant Transcriptome in Brassica juncea - Garima Sharma; Pooja Gokhale Sinha; Vartika Mathur (Journal of Plant Growth Regulation, 2024)

Interplay mechanism of exogenous hydrogen sulfide and nitric oxide in modulating ascorbate–glutathione cycle under nickel-induced oxidative stress in two paddy field cyanobacteria - Garima Singh; Sheo Mohan Prasad (Journal of Plant Biochemistry and Biotechnology, 2024)

Risk assessment of uranium in water sources near coal mines and in human organs of Shahdol District, Madhya Pradesh, using biokinetic modelling - Garima; Babita; Amanjeet; Navish Kataria; Ashutosh Bhardwaj; Rekha Dhiman; Sawan Chaudhary (Environmental Geochemistry and Health, 2024)

Tectonomagmatic evolution of Pune – Nasik Deccan Dykes: Insights from structure and dimension scaling - Ragini Kumari; Jyotirmoy Mallik; Garima Shukla (Tectonophysics, 2024)

Mechanistic insights to Paenibacillus lentimorbus mediated biocontrol of Alternaria solani in Solanum lycopersicum L. through carbohydrate reallocation and sweet immunity suppression - Garima Gupta; Harshita Joshi; Shashank Kumar Mishra; Puneet Singh Chauhan (Physiological and Molecular Plant Pathology, 2024)

Theoretical and earthquake-induced groundwater chemistry changes: A perspective - Sachita Baniya; Shukra Raj Paudel; Michael J. Angove; Garima Acharya; Amrita Wagle; Manita Khatri; Huu Hao Ngo; Wenshan Guo; Bandita Mainali (Journal of Hydrology, 2024)

Correction to: Conserving industrially important endangered medicinal herb Trillium govanianum (Himalayan Trillium) through biotechnological based interventions - Vinay Kumar; Garima; Rajnish Sharma; Aayushee Thakur; Parul Sharma; Yash Pal Sharma; Anamika Thakur; Sneh Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Nanopriming with phytofabricated selenium nanoparticles alleviates arsenite-induced oxidative stress in Spinacia oleracea L - Amit Kumar; Garima Jain; Prasanna Dutta; Puja Singh; Naushad Alam; Shiv Narayan; Pramod Arvind Shirke; Debasis Chakrabarty (Environmental Science and Pollution Research, 2024)

A time and temperature dependent biosynthesis of silver nanoparticles using the extract of Platycladus orientalis’ fruit - Deepa; Madhur Babu Singh; Gauri Thakur; Anirudh Pratap Singh Raman; Prashant Singh; Pradeep Kumar; Ravinder Singh; Garima Pandey; Kamlesh Kumari (Next Research, 2024)

Occurrence, Toxicodynamics, and Mechanistic Insights for Atrazine Degradation in the Environment - Garima Gajendra; Mrudula Pulimi; Chandrasekaran Natarajan; Amitava Mukherjee (Water, Air, & Soil Pollution, 2024)

Conserving industrially important endangered medicinal herb Trillium govanianum (Himalayan Trillium) through biotechnological based interventions - Vinay Kumar; Garima; Rajnish Sharma; Aayushee Thakur; Parul Sharma; Yash Pal Sharma; Anamika Thakur; Sneh Sharma (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

Identification of lncRNAs regulating seed traits in Brassica juncea and development of a comprehensive seed omics database - Pinky Yadav; Prachi Priyam; Garima Yadav; Abhinandan Yadav; Rubi Jain; Satyam Sunderam; Manoj Kumar Sharma; Inderjeet Kaur; Namrata Dhaka (Functional & Integrative Genomics, 2024)

Mineralogy and whole-rock geochemistry of the Oligocene Barail Group of rocks of Belt of Schuppen, Northeast India: Implications for tectono-provenance and paleo-weathering - Manash Pratim Gogoi; Yunpeng Dong; Pradip Borgohain; Devojit Bezbaruah; Arvind Pandey; Yadav Krishna Gogoi; Garima Konwar; Gautam Raj Bawri; Bubul Bharali (Acta Geochimica, 2024)

Synthetic Short Cryptic Antimicrobial Peptides as Templates for the Development of Novel Biotherapeutics Against WHO Priority Pathogen - Manjul Lata; Vrushti Telang; Pooja Gupta; Garima Pant; Mitra Kalyan; Jesu Arockiaraj; Mukesh Pasupuleti (International Journal of Peptide Research and Therapeutics, 2024)

Fungal pathogen: A game changer for insect herbivore in sequential attack on tomato - Phyoe Wai Htun; Garima Sharma; Vartika Mathur (South African Journal of Botany, 2024)

Diet composition and variation in four commonly landed and threatened shark species in Maharashtra, India - Garima Bora; Shawn Dsouza; Kartik Shanker (Regional Studies in Marine Science, 2024)

Boron nitride and its functionalized derivatives: An overview and comparative assessment of their structure, properties and application with a special focus as water-based adsorbent - Brij Bhushan; Arunima Nayak; Garima Bhatnagar; Anshika Chauhan; Deepika Kashyap (Journal of Water Process Engineering, 2024)

Tailoring polymeric nanocarriers for hypoxia-specific drug release: Insights into design and applications in clinics - Jomon George Joy; Garima Sharma; Jin-Chul Kim (Chemical Engineering Journal, 2024)

Chitosan nanofertilizer to strengthen sink strength and provide resistance against PFSR (post flowering stalk rot) disease in maize - Garima Sharma; Vinod Saharan; Ajay Pal; S.S. Sharma (Biocatalysis and Agricultural Biotechnology, 2024)

Effect of feeding chitosan and blend of essential organic acids on growth performance, haematological parameters and innate immunity in early aged male layer chicks - Garima Chahar; Sidhartha Deshmukh; H. S. Banga; Paviter Kaur (Tropical Animal Health and Production, 2024)

Bryophyllum pinnatum (Lam.) Oken: unravelling therapeutic potential and navigating toxicity - Garima Sharma; Alka Jangra; Sonia Sihag; Siddhant Chaturvedi; Shalu Yadav; Vinod Chhokar (Physiology and Molecular Biology of Plants, 2024)

Statistical Modelling of Thermostable Cellulase Production Conditions of Thermophilic Geobacillus sp. TP-1 Isolated from Tapovan Hot Springs of the Garhwal Himalayan Mountain Ranges, India - Meghna Arya; Garima Chauhan; Tazeem Fatima; Digvijay Verma; Monica Sharma (Indian Journal of Microbiology, 2024)

Statistical optimization of bioprocess parameters for enhanced production of bacterial cellulose from K. saccharivorans BC-G1 - Samriddh Srivastava; Garima Mathur (Brazilian Journal of Microbiology, 2024)

Crosstalk mechanism of hydrogen sulfide and nitric oxide in regulating the nickel induced toxicity of cyanobacteria Nostoc muscorum and Anabaena sp. - Garima Singh; Sheo Mohan Prasad (Acta Physiologiae Plantarum, 2024)

Advances in metallopolymers: Synthesis strategies, catalytic insights, and environmental remediation applications - Mohd Aslam; Anjali Rani; Javed Khan; Ritika Sharma; Bhaskara Nand Pant; Prashant Singh; Vinod Kumar; Garima Pandey; Bhawna (Sustainable Chemistry and Pharmacy, 2024)

Valorization of Spent Mushroom Substrate (SMS) as a sustainable approach to remediation of xenobiotic compounds in groundwater - A comprehensive review - Garima Gupta; Sandhya Maurya; Prabhat Nath Jha; Puneet Singh Chauhan (Groundwater for Sustainable Development, 2024)

The efficacy of non-equilibrium dielectric barrier discharge in air on the elimination of phytopathogenic fungi from wooden surface - Irena Maliszewska; Daria Nowinski; Jiří Fujera; Garima Arora; Milan Šimek; Tomasz Czapka (Food Control, 2024)

Recent advancement of nano-biochar for the remediation of heavy metals and emerging contaminants: Mechanism, adsorption kinetic model, plant growth and development - Himanshu K. Pathak; Chandra Shekhar Seth; Prabhat K. Chauhan; Gopal Dubey; Garima Singh; Devendra Jain; Sudhir K. Upadhyay; Padmanabh Dwivedi; Kuan Shiong Khoo (Environmental Research, 2024)

Downregulation of ATF-4 Attenuates the Endoplasmic Reticulum Stress–Mediated Neuroinflammation and Cognitive Impairment in Experimentally Induced Alzheimer’s Disease Model - Poonam Goswami; Juheb Akhter; Anuradha Mangla; Suramya Suramya; Garima Jindal; Shahzad Ahmad; Sheikh Raisuddin (Molecular Neurobiology, 2024)

A critical review of the edible seaweed Palmaria palmata (L.) Weber & Mohr and its bioactive compounds in the “omics” era - Maonian Xu; Yuetuan Zhang; Bing Wu; Yidan Zhang; Mingyu Qiao; Garima Singh; Elín Soffía Ólafsdóttir; Snæbjörn Pálsson; Starri Heiðmarsson; Hugo de Boer; Margrét Þorsteinsdóttir; Guðjón Þorkelsson; et al. (Algal Research, 2024)

Decoding the TAome and computational insights into parDE toxin-antitoxin systems in Pseudomonas aeruginosa - Nomita Gupta; Mohit Yadav; Garima Singh; Shobhi Chaudhary; Chaitali Ghosh; Jitendra Singh Rathore (Archives of Microbiology, 2024)

Bioprospecting of ornamental and weed plants for hydroxynitrile lyase activity and characterization of novel hydroxynitrile lyases (HNLs) of Euphorbia mili and Cascabela thevetia - Asha Kumari; Yash Vardhan Shukla; Garima Chauhan; Meghna Arya; Monica Sharma (Vegetos, 2024)

Host-specific endophytes of Momordica charantia: A promising source for affordable lung cancer therapeutics - Garima Sharma; Rashmi Bhardwaj; Jyoti; Vitthal T. Barvkar; Rucha C. Godbole; Vinay Kumar; Vartika Mathur (South African Journal of Botany, 2024)

Bioinformatics insight in shallow genome sequence: a case study of Corymbia hybrid (C. citriodora × C. torelliana) - Arzoo Shamoon; Maneesh S. Bhandari; Garima Mishra; Rajendra K. Meena; Shailesh Pandey (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Detection of HbD Punjab Trait in Saurashtra Region of Gujarat by HPLC Method - Sagar Dholariya; Deepak N. Parchwani; Amit Sonagra; Ragini Singh; Anita Motiani; Mehul Kaliya; Garima Anandani (Indian Journal of Clinical Biochemistry, 2024)

Urine Metabolomics Reveals Overlapping Metabolic Associations Between Preeclampsia and Gestational Diabetes - Nupur Rani Agarwal; Garima Kachhawa; Bolaji Fatai Oyeyemi; Neel Sarovar Bhavesh (Indian Journal of Clinical Biochemistry, 2024)

Pythium oligandrum induces growth promotion in starch potato without significantly altering the rhizosphere microbiome - Christian B. Andersen; Kristin Aleklett; Garima Digdarshika; Åsa Lankinen; Laura J. Grenville-Briggs (Applied Soil Ecology, 2024)

Laser-disintegrated copper-activated salicylic acid (Cu-SA) nanoparticles suppressed the seed-borne pathogens of rice with enhanced seed invigoration parameters - Garima Gandhi; Anjali Sidhu; Urvashi Bhardwaj; Mehra S. Sidhu; Anju Bala Sharma; Varinder Khepar (Environmental Science and Pollution Research, 2024)

Recent advances in photocatalytic removal of antiviral drugs by Z-scheme and S-scheme heterojunction - Garima Rana; Pooja Dhiman; Amit Kumar; Ankush Chauhan; Gaurav Sharma (Environmental Science and Pollution Research, 2024)

Optimizing MSW incineration bottom ash reuse: A study on treated wastewater washing and leaching control - Deepesh Bansal; Garima Gupta; G.V. Ramana; Manoj Datta (Waste Management, 2024)

Gene therapy: an alternative to treat Alzheimer’s disease - Vanshika Doshi; Garima Joshi; Sanjay Sharma; Deepak Choudhary (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Financing Climate-Smart Agriculture: a case study from the Indo-Gangetic Plains - Roberto Villalba; Garima Joshi; Thomas Daum; Terese E. Venus (Mitigation and Adaptation Strategies for Global Change, 2024)
The Indo-Gangetic Plains represents one of South Asia’s most productive agricultural regions, yet it is highly vulnerable to climate change and requires the widespread adoption of Climate-Smart Agriculture. Although farmers understand the benefits of such technologies, financial constraints often undermine adoption. Using a case study from Haryana, we assess the opportunities and challenges aligned with the different pathways available for farmers to adopt and finance two capital-intensive technologies: laser land levelers and happy seeders. Our analysis uses unique data from Karnal, where stakeholders have partnered in Climate-Smart-Villages, and combines a household survey from 120 farmers, interviews, and focus group discussions with banks and cooperatives. Our results indicate adoption rates of 77% for laser land levelers and 52% for happy seeders, with only 7% and 21% of farmers owning the technologies, respectively. Hiring is highly preferred over purchase, mainly due to the flourishing of Custom-Hiring Centers, which are vital in driving large-scale implementation. We find that farmers prefer funding from family, savings, and moneylenders (indirect pathways) rather than from commercial banks (direct pathways) to get immediate access to credit and avoid bureaucratic procedures. Our study offers broader insights into the state of agricultural finance in India and adaptation to climate change and reveals that institutional innovations can enhance the financing of CSA technologies for smallholder farmers. Our findings have important implications for decision-makers seeking to streamline credit access for CSA machinery rental. Future research should focus on the efficacy of different finance channels and their causal impact on pathways for technology adoption.

Nanocellulose extraction from lignocellulosic materials and its potential applications: a review - Garima Joshi; S. R. Shukla; Shakti Singh Chauhan (Journal of the Indian Academy of Wood Science, 2024)

Environmentally responsible disposal and reuse of MSW incineration bottom ash: assessment from two Indian plants - Deepesh Bansal; Garima Gupta; G. V. Ramana; Manoj Datta (Clean Technologies and Environmental Policy, 2024)

Synergistic regulation of hydrogen sulfide and nitric oxide on biochemical components, exopolysaccharides, and nitrogen metabolism in nickel stressed rice field cyanobacteria - Garima Singh; Sheo Mohan Prasad (Journal of Plant Research, 2024)

Prospects of probiotics in beekeeping: a review for sustainable approach to boost honeybee health - Smriti; Anita Rana; Gagandeep Singh; Garima Gupta (Archives of Microbiology, 2024)

Pre-clinical evaluation of 99mTc-labeled chalcone derivative for amyloid-β imaging post-head trauma - Garima Mann; Shivani Daksh; Nikhil Kumar; Ankur Kaul; B. G. Roy; M. Thirumal; Anupama Datta (JBIC Journal of Biological Inorganic Chemistry, 2024)

Mycelium-based biocomposites: synthesis and applications - Monica Sharma; Srasti Verma; Garima Chauhan; Meghna Arya; Asha Kumari (Environmental Sustainability, 2024)

Genome-wide identification and expression analysis of autophagy-related genes (ATG) in Gossypium spp. reveals their crucial role in stress tolerance - Mamta Yadav; Garima Saxena; Rishi Kumar Verma; Mehar H. Asif; Vijay Pratap Singh; Samir V. Sawant; Surendra Pratap Singh (South African Journal of Botany, 2024)

Elucidating the prospects of paddy straw as a potential source of nanosilica: A road map towards sustainable agriculture, bioeconomy and entrepreneurship - Garima Singh; Kanika Chowdhary; Satyawati Sharma (Journal of Cleaner Production, 2024)

Atmospheric deposition of mineral dust and associated nutrients over the Equatorial Indian Ocean - Prema Piyusha Panda; Garima Shukla; Ashwini Kumar; M.A. Aswini; Ankush Kaushik; Gourav Nayak; Vishnu Murthy Matta (Science of The Total Environment, 2024)

Food grade plastics and Bisphenol A: Associated risks, toxicity, and bioremediation approaches - Preksha Palsania; Kirti Singhal; Mohd Ashaf Dar; Garima Kaushik (Journal of Hazardous Materials, 2024)

Convolutional Neural Networks Guided Raman Spectroscopy as a Process Analytical Technology (PAT) Tool for Monitoring and Simultaneous Prediction of Monoclonal Antibody Charge Variants - Nitika Nitika; B. Keerthiveena; Garima Thakur; Anurag S. Rathore (Pharmaceutical Research, 2024)

Assessing vegetation health in dry tropical forests of Rajasthan using remote sensing - Garima Toor; Neha Goyal Tater; Tarush Chandra (Applied Geomatics, 2024)

Identification and physico-chemical characterization of microplastics in marine aerosols over the northeast Arabian Sea - Ankush Kaushik; Priyansha Gupta; Ashwini Kumar; Mahua Saha; Emil Varghese; Garima Shukla; K. Suresh; Sachin S. Gunthe (Science of The Total Environment, 2024)

Sustainable phycoremediation of mushroom farm wastewater using novel isolated microalga (Chlamydomonas asymmetrica SAG70.72): Experimental and kinetic studies - Sadeq K. Alhag; Garima Kumari; Deep Gupta; Eman A. Al-Shahari; Laila A. Al-Shuraym; Mohamed T. Ahmed; Ibtisam M. Alsudays; Sudhir Kumar Gaur; Sami Abou Fayssal; Ivan Širić; Pankaj Kumar; Ebrahem M. Eid (Journal of Water Process Engineering, 2024)

Polysaccharides from red seaweeds: Effect of extraction methods on physicochemical characteristics and antioxidant activities - Amal D. Premarathna; Tamer A.E. Ahmed; Garima Kulshreshtha; Sanjida Humayun; Clarisa Naa Shormeh Darko; Vitalijs Rjabovs; Riadh Hammami; Alan T. Critchley; Rando Tuvikene; Maxwell T. Hincke (Food Hydrocolloids, 2024)

Functional connectivity in northern swamp deer (Rucervus duvaucelii duvaucelii) population across a fragmented, human-dominated landscape along Gangetic Plains of north India: implications for conservation in non-protected areas - Shrutarshi Paul; Sohini Saha; Parag Nigam; Garima Pandey; Bilal Habib; Dhananjai Mohan; Bivash Pandav; Samrat Mondol (Conservation Genetics, 2024)

Deciphering mucin degrading ability and safety aspects of enterococcus strain from human feces - Garima Deswal; Harsha Nirvan; Manjit K. Selwal; Krishan Kumar Selwal (Biologia, 2024)

Root exudates, the warrior of plant life: Revolution below the ground - Garima Balyan; Akhilesh Kumar Pandey (South African Journal of Botany, 2024)

Metaverse for Sustainable Development in a bibliometric analysis and systematic literature review - Amar Johri; Parikshit Joshi; Shailendra Kumar; Garima Joshi (Journal of Cleaner Production, 2024)

One-pot synthesis and in vitro bioactivity of novel 4-aminopyrazolo[3,4-b]pyridine derivatives as potential antimicrobial compounds - Ranjana Aggarwal; Suresh Kumar; Garima Sumran; Deepansh Sharma (Medicinal Chemistry Research, 2024)

Emission inventory of inorganic trace gases from solid residential fuels over the National Capital Territory of India - Rahul Arya; Sakshi Ahlawat; Lokesh Yadav; Martina Rani; Arnab Mondal; Ritu Jangirh; Garima Kotnala; Nikki Choudhary; Akansha Rai; Ummed Singh Saharan; Pooja Yadav; Rubiya Banoo; et al. (Environmental Science and Pollution Research, 2023)

Assessment of fluoride exposure and associated health risks from different sources of drinking water to various age groups in Bathinda City, Punjab, India - Vikas Duggal; Tanisha Goyal; Ramandeep Kaur; Jashandeep Kaur; Garima Bajaj (Physics and Chemistry of the Earth, Parts A/B/C, 2023)

Development of biodegradable tableware from novel combination of paddy straw and pine needles: A potential alternative against plastic cutlery - Akansha Gupta; Garima Singh; Pooja Ghosh; Kalpana Arora; Satyawati Sharma (Journal of Environmental Chemical Engineering, 2023)

New face in the row of bioactive compounds and toxin-antitoxin modules: Xenorhabdus nematophila - Shobhi Chaudhary; Garima Singh; Nomita Gupta; Chaitali Ghosh; Jitendra Singh Rathore (Journal of Asia-Pacific Entomology, 2023)

Identification and functional characterization of a novel aldo–keto reductase from Aloe vera - Alka Jangra; Siddhant Chaturvedi; Sonia Sihag; Garima Sharma; Siddharth Tiwari; Vinod Chhokar (Planta, 2023)

SPAD Chlorophyll Meter-Based Real-Time Nitrogen Management in Manure-Amended Lowland Rice - Mainak Ghosh; Arnab Roychowdhury; Swaraj Kumar Dutta; Kali Krishna Hazra; Garima Singh; Anshuman Kohli; Sanjay Kumar; Shivashankar Acharya; Jajati Mandal; Yanendra Kumar Singh; Sushil Kumar Pathak; Sanjeev Kumar Gupta (Journal of Soil Science and Plant Nutrition, 2023)

Genetic evaluation and characterization of anatomical and physicochemical properties in Grevillea robusta: an alternative commercial agroforestry species - Maneesh S. Bhandari; Aman Dabral; Sandeep Maikhuri; Anchal Bisht; Garima Thapliyal; Rama Kant; Rajendra K. Meena; Dheerendra Kumar; Vikas Rana (Journal of the Indian Academy of Wood Science, 2023)

The Trail-Following Communication in Stylotermes faveolus and S. halumicus (Blattodea, Isoptera, Stylotermitidae) - Himanshu Thakur; Surbhi Agarwal; Jaromír Hradecký; Garima Sharma; Hou-Feng Li; Shang-En Yang; Hana Sehadová; Ravinder S. Chandel; Mirek Hyliš; Vartika Mathur; Jan Šobotník; David Sillam-Dussès (Journal of Chemical Ecology, 2023)

Remote sensing-enabled machine learning for river water quality modeling under multidimensional uncertainty - Saiful Haque Rahat; Todd Steissberg; Won Chang; Xi Chen; Garima Mandavya; Jacob Tracy; Asphota Wasti; Gaurav Atreya; Shah Saki; Md Abul Ehsan Bhuiyan; Patrick Ray (Science of The Total Environment, 2023)

Exploring the status of global terrestrial and aquatic microbial diversity through ‘Biodiversity Informatics’ - Chiranjib Chakraborty; Ashish Ranjan Sharma; Garima Sharma; Manojit Bhattacharya; Sang-Soo Lee (Environment, Development and Sustainability, 2023)

Silicon and salicylic acid: individual and combined impact on plant growth and stress tolerance - Sunita Rawat; Ravita; Kalpana Tyagi; Kishan Kumar; Garima Kumari; Sudhan Singh Kaintura; Amit Pandey; Harish Singh Ginwal; Santan Barthwal (Plant Biosystems, 2023)

Methane consumption under the influence of different nitrogen sources in a tropical soil ecosystem - Bharati Kollah; Himanshi Verma; Rakesh Parmar; Mayanglambam Homeshwari Devi; Nagvanti Atoliya; Apekcha Bajpai; K.C. Shinoji; Amar Bahadur Singh; Ashok Patra; Devendra Jain; Garima Dubey; Santosh Ranjan Mohanty (Pedobiologia, 2023)

Harnessing cyanobacterium-fungal interactions to develop potting mixes for disease-free tomato nursery - Jyoti Shukla; Udita Gulia; Himani Gupta; Krati Gupta; Robin Gogoi; Arun Kumar; Himanshu Mahawar; Sekar Nishanth; Garima Saxena; Awani Kumar Singh; Lata Nain; Yashbir Singh Shivay; et al. (Phytoparasitica, 2023)

Modelling of the Himalayan Mountain river basin through hydro-morphological and compound factor-based approaches using geoinformatics tools - Parvaiz Ahmad Ganie; Ravindra Posti; Kishor Kunal; Garima Kunal; Vidya Shree Bharti; Vinay Kumar Sehgal; Debajit Sarma; Pramod Kumar Pandey (Modeling Earth Systems and Environment, 2023)

siRNA-Based Novel Therapeutic Strategies to Improve Effectiveness of Antivirals: An Insight - Krittika Chatterjee; Sagheerah Lakdawala; Sheikh Shahnawaz Quadir; Dinesh Puri; Dinesh Kumar Mishra; Garima Joshi; Sanjay Sharma; Deepak Choudhary (AAPS PharmSciTech, 2023)

Low environmental impact remediation of microplastics: Visible-light photocatalytic degradation of PET microplastics using bio-inspired C,N-TiO2/SiO2 photocatalysts - Maria Camila Ariza-Tarazona; Cristina Siligardi; Hugo Alejandro Carreón-López; José Enrique Valdéz-Cerda; Paolo Pozzi; Garima Kaushik; Juan Francisco Villarreal-Chiu; Erika Iveth Cedillo-González (Marine Pollution Bulletin, 2023)

Characterization of MSW incineration bottom ash for use as structural fill in reinforced soil structures: Geoenvironmental, geotechnical and economical assessment - Deepesh Bansal; G.V. Ramana; Manoj Datta; Garima Gupta (Waste Management, 2023)

Biodegradable redox sensitive chitosan based microgels for potential agriculture application - Ankita Dhiman; Dimpy Bhardwaj; Kajal Goswami; Deepika; Garima Agrawal (Carbohydrate Polymers, 2023)

Rottlerin renders a selective and highly potent CYP2C8 inhibition to impede EET formation for implication in cancer therapy - Diksha Manhas; Shipra Bhatt; Garima Rai; Vinay Kumar; Sahil Bharti; Sumit Dhiman; Shreyans K. Jain; Deepak K. Sharma; Probir Kumar Ojha; Sumit G. Gandhi; Anindya Goswami; Utpal Nandi (Chemico-Biological Interactions, 2023)

Tempol and silymarin rescue from zinc-induced degeneration of dopaminergic neurons through modulation of oxidative stress and inflammation - Garima Singh; Namrata Mittra; Chetna Singh (Molecular and Cellular Biochemistry, 2023)

Perspective: The unexplored dimensions behind the foam formation in River Yamuna, India - Garima Sejwal; Santosh Kumar Singh (Environmental Science and Pollution Research, 2023)

SEFWaM–deep learning based smart ensembled framework for waste management - Sujal Goel; Anannya Mishra; Garima Dua; Vandana Bhatia (Environment, Development and Sustainability, 2023)

Efficient Agrobacterium tumefaciens-mediated genetic transformation of Aloe vera - Alka Jangra; Siddhant Chaturvedi; Garima Sharma; Sonia Sihag; Siddharth Tiwari; Vinod Chhokar (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Exploring recent trends in integrating urban planning and ecology - Garima Toor; Neha Goyal Tater; Tarush Chandra (Environment, Development and Sustainability, 2023)

Land suitability modelling for rainbow trout farming in the Eastern Himalayan Region, India, using GIS–MCE approach - Parvaiz Ahmad Ganie; Ravindra Posti; Deepjyoti Baruah; Kishor Kunal; Garima Kunal; Debajit Sarma; Pramod Kumar Pandey (Modeling Earth Systems and Environment, 2023)

Synergistic soil-less medium for enhanced yield of crops: a step towards incorporating genomic tools for attaining net zero hunger - Nitika Thakur; Mohit Nigam; Garima Awasthi; Aryan Shukla; Anis Ali Shah; Nidhi Negi; Sher Aslam Khan; Ryan Casini; Hosam O. Elansary (Functional & Integrative Genomics, 2023)

Arabidopsis plants overexpressing additional copies of heat shock protein Hsp101 showed high heat tolerance and endo-gene silencing - Richa Babbar; Lalit Dev Tiwari; Ratnesh Chandra Mishra; Rinchuila Shimphrui; Aditya Abha Singh; Isha Goyal; Surbhi Rana; Ritesh Kumar; Vijyesh Sharma; Gayatri Tripathi; Lisha Khungar; Jaydeep Sharma; et al. (Plant Science, 2023)

Temporal trends in the use and concentration of organophosphorus pesticides in Indian riverine water, toxicity, and their risk assessment - Mohd Ashraf Dar; Burhan Hamid; Garima Kaushik (Regional Studies in Marine Science, 2023)

Unlocking the microbial studies through computational approaches: how far have we reached? - Rajnish Kumar; Garima Yadav; Mohammed Kuddus; Ghulam Md Ashraf; Rachana Singh (Environmental Science and Pollution Research, 2023)

Toxicity evaluation of iron oxide nanoparticles to freshwater cyanobacteria Nostoc ellipsosporum - Mukesh Kumar; Kunal Seth; Sunita Choudhary; Geetanjali Kumawat; Subhasha Nigam; Garima Joshi; Vinod Saharan; Mukesh Meena; Amit Kumar Gupta; Harish (Environmental Science and Pollution Research, 2023)

Development of clove oil based nanoencapsulated biopesticide employing mesoporous nanosilica synthesized from paddy straw via bioinspired sol-gel route - Garima Singh; Himanshu Arora; Hariprasad P.; Satyawati Sharma (Environmental Research, 2023)

Genome-wide characterization leading to simple sequence repeat (SSR) markers development in Shorea robusta - Garima Mishra; Rajendra K. Meena; Rama Kant; Shailesh Pandey; Harish S. Ginwal; Maneesh S. Bhandari (Functional & Integrative Genomics, 2023)

Transcription factors controlling the expression of oxidative stress associated genes in rice (Oryza sativa L.) - D. Sujitha; H. G. Jalendra Kumar; Garima Thapliayal; Garima Pal; P. A. Vanitha; Akshay Uttarkar; Mahesh Patil; B. H. Rajashekar Reddy; Vidya Niranjan; Usha Rayalcheruvu; Geetha Govind; M. Udayakumar; et al. (Plant Biotechnology Reports, 2023)

Bulk and in-situ chemical analysis of meteorite Berduc, an L6 chondrite - Amit Basu Sarbadhikari; Garima Arora; Maria E Varela; Ramakant R Mahajan (Journal of Earth System Science, 2023)

An active solar desalination system integrated with collective condenser heat pipe solar evacuated tube collector: a thermoeconomic analysis - Garima Nema; Karunamurthy Krishnasamy (Environmental Science and Pollution Research, 2023)

“Magnetic Ni–Zn ferrite anchored on g-C3N4 as nano-photocatalyst for efficient photo-degradation of doxycycline from water” - Pooja Dhiman; Garima Rana; Razan A. Alshgari; Amit Kumar; Gaurav Sharma; Mu. Naushad; Zeid A. ALOthman (Environmental Research, 2023)

First synthetic report and antioxidant potential of natural product (±)-5,7-dihydroxy-8-methyl-3-(2',4'-dihydroxybenzyl)chroman-4-one from Chinese medicine Gan Luo Xin pill - Ninad V. Puranik; Garima Mishra; Swapnaja Gulawani; Pratibha Srivastava (Natural Product Research, 2022)

Carbon nanotube-based nano-biosensors for detecting heavy metals in the aquatic environment - Rushikesh L. Chopade; Pritam P. Pandit; Varad Nagar; Vinay Aseri; Badal Mavry; Anuj Sharma; Apoorva Singh; Rohit Kumar Verma; Garima Awasthi; Kumud Kant Awasthi; Mahipal Singh Sankhla (Environmental Science and Pollution Research, 2022)

Insights into the morphometric characteristics of the Himalayan River using remote sensing and GIS techniques: a case study of Saryu basin, Uttarakhand, India - Parvaiz Ahmad Ganie; Ravindra Posti; Kishor Kunal; Garima Kunal; Debajit Sarma; Pramod Kumar Pandey (Applied Geomatics, 2022)

Long-Term (2013–2018) Relationship of Water-Soluble Inorganic Ionic Species of PM2.5 with Ammonia and Other Trace Gases in Delhi, India - Garima Kotnala; S. K. Sharma; T. K. Mandal (Aerosol Science and Engineering, 2022)

Effect of planting seasons and growing conditions on performance of yacon (Smallanthus sonchifolius) in sub tropical Indian Himalayas - Bhupender Dutt; Rajneesh Kumar; Garima; Yourmila Kumari (Vegetos, 2022)

Komagataeibacter saccharivorans strain BC-G1: an alternative strain for production of bacterial cellulose - Samriddh Srivastava; Garima Mathur (Biologia, 2022)

Simulation of Land Surface Temperature Patterns Over Future Urban Areas—A Machine Learning Approach - Sandeep Maithani; Garima Nautiyal; Archana Sharma; Surendra Kumar Sharma (Journal of the Indian Society of Remote Sensing, 2022)

Optimizing the malathion degrading potential of a newly isolated Bacillus sp. AGM5 based on Taguchi design of experiment and elucidation of degradation pathway - Mohd Ashraf Dar; Garima Kaushik (Biodegradation, 2022)

Evaluating complete surface-associated and secretory proteome of Leishmania donovani for discovering novel vaccines and diagnostic targets - Munawwar Karim; Garima Singh; Shweta Thakur; Aarti Rana; Abdur Rub; Yusuf Akhter (Archives of Microbiology, 2022)

Transcriptomic Insight into Aroma Pathway Genes and Effect of Ripening Difference on Expression of Aroma Genes in Different Mango Cultivars - Garima Pathak; Shivanand Suresh Dudhagi; Saumya Raizada; Vidhu A. Sane (Plant Molecular Biology Reporter, 2022)

RP-HPLC estimation of thermal oxidation of thymoquinone in Nigella sativa with reference to its antioxidant potential and vis-a-vis in-vitro DNA damage inhibition - Mohammed Shariq Iqbal; Anjuman Gul Memon; Ausaf Ahmad; Garima Gupta; Zahra Iqbal (Plant Physiology Reports, 2022)

Recruiting endophytic bacteria of wetland plants to phytoremediate organic pollutants - Tanvi Singh; Garima Awasthi; Yamini Tiwari (International Journal of Environmental Science and Technology, 2022)

Bintaro (Cerbera odollam and Cerbera manghas): an overview of its eco-friendly use, pharmacology, and toxicology - Mansi Saxena; Ekta B. Jadhav; Mahipal Singh Sankhla; Muskan Singhal; Kapil Parihar; Kumud Kant Awasthi; Garima Awasthi (Environmental Science and Pollution Research, 2022)

Heavy metals in vegetables: a review of status, human health concerns, and management options - Seema Manwani; Pooja Devi; Tanvi Singh; Chandra Shekhar Yadav; Kumud Kant Awasthi; Narain Bhoot; Garima Awasthi (Environmental Science and Pollution Research, 2022)

Mercury occurrence in drinking water resources of Ganga Alluvial Plain, northern India - Vandana Devi; Mohammad Mohsin Atique; Garima Upreti; Jitendra Kumar Yadav; Satyendra Singh; Dharmendra Kumar Jigyasu; Munendra Singh (Sustainable Water Resources Management, 2022)

Biodegradation of malathion by Micrococcus sp. strain MAGK3: kinetics and degradation fragments - Mohd Ashraf Dar; Jeky Chanwala; Prem Raj Meena; Arvind Pratap Singh; Garima Kaushik (Archives of Microbiology, 2022)

Process Analytical Technology (PAT) Implementation for Membrane Operations in Continuous Manufacturing of mAbs: Model-Based Control of Single-Pass Tangential Flow Ultrafiltration - Garima Thakur; Vishnu Masampally; Amey Kulkarni; Anurag S. Rathore (The AAPS Journal, 2022)

Identification and characterization of chickpea genotypes for early flowering and higher seed germination through molecular markers - Garima Yadav; Deepanshu Jayaswal; Kuldip Jayaswall; Abhishek Bhandawat; ArvindNath Singh; Jyotsana Tilgam; Abhishek Kumar Rai; Rachna Chaturvedi; Ashutosh Kumar; Sanjay Kumar; S. P. Jeevan Kumar (Molecular Biology Reports, 2022)

Signaling molecules hydrogen sulfide (H2S) and nitric oxide (NO): role in microalgae under adverse environmental conditions - Garima Singh; Anuradha Patel; Sanjesh Tiwari; Divya Gupta; Sheo Mohan Prasad (Acta Physiologiae Plantarum, 2022)

Nano-strategies as Oral Drug Delivery Platforms for Treatment of Cancer: Challenges and Future Perspectives - Sheikh Shahnawaz Quadir; Vinod Saharan; Deepak Choudhary; Harish; C. P. Jain; Garima Joshi (AAPS PharmSciTech, 2022)

The dark side of miracle plant-Aloe vera: a review - Alka Jangra; Garima Sharma; Sonia Sihag; Vinod Chhokar (Molecular Biology Reports, 2022)

Mitochondrial Dysfunction Contributes To Zinc-induced Neurodegeneration: a Link with NADPH Oxidase - Amit Kumar Chauhan; Namrata Mittra; Garima Singh; Chetna Singh (Journal of Molecular Neuroscience, 2022)

Hypobaric Hypoxia Induces Deficits in Adult Neurogenesis and Social Interaction via Cyclooxygenase-1/ EP1 Receptor Pathway Activating NLRP3 Inflammasome - Garima Chauhan; Gaurav Kumar; Koustav Roy; Punita Kumari; Bhanuteja Thondala; Krishna Kishore; Usha Panjwani; Koushik Ray (Molecular Neurobiology, 2022)

ZnO-based heterostructures as photocatalysts for hydrogen generation and depollution: a review - Pooja Dhiman; Garima Rana; Amit Kumar; Gaurav Sharma; Dai-Viet N. Vo; Mu. Naushad (Environmental Chemistry Letters, 2022)

Climate change effect on soil carbon stock in different land use types in eastern Rajasthan, India - Garima Sharma; L. K. Sharma (Environment, Development and Sustainability, 2022)

Gridded distribution of total suspended particulate matter (TSP) and their chemical characterization over Delhi during winter - Ritu Jangirh; Sakshi Ahlawat; Rahul Arya; Arnab Mondal; Lokesh Yadav; Garima Kotnala; Pooja Yadav; Nikki Choudhary; Martina Rani; Rubiya Banoo; Akansha Rai; Ummed Singh Saharan; et al. (Environmental Science and Pollution Research, 2022)

Biosorptive and Biodegradative Mechanistic Approach for the Decolorization of Congo Red Dye by Aspergillus Species - Garima Singh; S. K. Dwivedi (Bulletin of Environmental Contamination and Toxicology, 2022)

Implementation of Genetic Engineering and Novel Omics Approaches to Enhance Bioremediation: A Focused Review - Garima Malik; Rahul Arora; Ritu Chaturvedi; Manoj S. Paul (Bulletin of Environmental Contamination and Toxicology, 2022)

Vitex negundo protects against cerebral ischemia–reperfusion injury in mouse via attenuating behavioral deficits and oxidative damage - Kamakshi Mehta; Deepak Prabhakar Bhagwat; Devraj; Palika Sehgal; Garima Mittal; Kapil Suchal (Psychopharmacology, 2022)

The Impact of Coenzyme Q10 on Neurodegeneration: a Comprehensive Review - Monika Kadian; Garima Sharma; Shivani Pandita; Kritika Sharma; Kanishka Shrivasatava; Neetu Saini; Anil Kumar (Current Pharmacology Reports, 2022)

Evaluation and Designing of Epitopic-Peptide Vaccine Against Bunyamwera orthobunyavirus Using M-Polyprotein Target Sequences - Pratik Ghosh; Manojit Bhattacharya; Prasanta Patra; Garima Sharma; Bidhan Chandra Patra; Sang-Soo Lee; Ashish Ranjan Sharma; Chiranjib Chakraborty (International Journal of Peptide Research and Therapeutics, 2022)

Testing a global standard for quantifying species recovery and assessing conservation impact - Molly K. Grace; H. Resit Akçakaya; Elizabeth L. Bennett; Thomas M. Brooks; Anna Heath; Simon Hedges; Craig Hilton‐Taylor; Michael Hoffmann; Axel Hochkirch; Richard Jenkins; David A. Keith; Barney Long; et al. (Conservation Biology, 2021)
Recognizing the imperative to evaluate species recovery and conservation impact, in 2012 the International Union for Conservation of Nature (IUCN) called for development of a “Green List of Species” (now the IUCN Green Status of Species). A draft Green Status framework for assessing species’ progress toward recovery, published in 2018, proposed 2 separate but interlinked components: a standardized method (i.e., measurement against benchmarks of species’ viability, functionality, and preimpact distribution) to determine current species recovery status (herein species recovery score ) and application of that method to estimate past and potential future impacts of conservation based on 4 metrics ( conservation legacy, conservation dependence , conservation gain , and recovery potential ). We tested the framework with 181 species representing diverse taxa, life histories, biomes, and IUCN Red List categories (extinction risk). Based on the observed distribution of species’ recovery scores, we propose the following species recovery categories : fully recovered, slightly depleted, moderately depleted, largely depleted, critically depleted, extinct in the wild, and indeterminate. Fifty‐nine percent of tested species were considered largely or critically depleted. Although there was a negative relationship between extinction risk and species recovery score, variation was considerable. Some species in lower risk categories were assessed as farther from recovery than those at higher risk. This emphasizes that species recovery is conceptually different from extinction risk and reinforces the utility of the IUCN Green Status of Species to more fully understand species conservation status. Although extinction risk did not predict conservation legacy, conservation dependence, or conservation gain, it was positively correlated with recovery potential. Only 1.7% of tested species were categorized as zero across all 4 of these conservation impact metrics , indicating that conservation has, or will, play a role in improving or maintaining species status for the vast majority of these species. Based on our results, we devised an updated assessment framework that introduces the option of using a dynamic baseline to assess future impacts of conservation over the short term to avoid misleading results which were generated in a small number of cases, and redefines short term as 10 years to better align with conservation planning. These changes are reflected in the IUCN Green Status of Species Standard.

Anti-mycobacterial activity evaluation of designed peptides: cryptic and database filtering based approach - Sneha Raj; Umamageswaran Venugopal; Garima Pant; Mitra Kalyan; Jesu Arockiaraj; Manju Y. Krishnan; Mukesh Pasupuleti (Archives of Microbiology, 2021)

Climate‐specific biosynthetic gene clusters in populations of a lichen‐forming fungus - Garima Singh; Anjuli Calchera; Meike Schulz; Moritz Drechsler; Helge B. Bode; Imke Schmitt; Francesco Dal Grande (Environmental Microbiology, 2021)
Summary Natural products can contribute to abiotic stress tolerance in plants and fungi. We hypothesize that biosynthetic gene clusters (BGCs), the genomic elements that underlie natural product biosynthesis, display structured differences along elevation gradients. We analysed biosynthetic gene variation in natural populations of the lichen‐forming fungus Umbilicaria pustulata . We collected a total of 600 individuals from the Mediterranean and cold‐temperate climates. Population genomic analyses indicate that U . pustulata contains three clusters that are highly differentiated between the Mediterranean and cold‐temperate populations. One entire cluster is exclusively present in cold‐temperate populations, and a second cluster is putatively dysfunctional in all cold‐temperate populations. In the third cluster variation is fixed in all cold‐temperate populations due to hitchhiking. In these two clusters the presence of consistent allele frequency differences among replicate populations/gradients suggests that selection rather than drift is driving the pattern. We advocate that the landscape of fungal biosynthetic genes is shaped by both positive and hitchhiking selection. We demonstrate, for the first time, the presence of climate‐associated BGCs and BGC variations in lichen‐forming fungi. While the associated secondary metabolites of the candidate clusters are presently unknown, our study paves the way for targeted discovery of natural products with ecological significance.

Divulging the Intricacies of Crosstalk Between NF-Kb and Nrf2-Keap1 Pathway in Neurological Complications of COVID-19 - Ranjana Bhandari; Garima Khanna; Dhriti Kaushik; Anurag Kuhad (Molecular Neurobiology, 2021)

Understanding the molecular evolution of tiger diversity through DNA barcoding marker ND4 and NADH dehydrogenase complex using computational biology - Chiranjib Chakraborty; Ashish Ranjan Sharma; Garima Sharma; Manojit Bhattacharya; Bidhan C. Patra; Bimal Kumar Sarkar; Saptarshi Banerjee; Kankana Banerjee; Sang-Soo Lee (Genes & Genomics, 2021)

Exploring the Relationship Between Spatio-temporal Land Cover Dynamics and Surface Temperature Over Dehradun Urban Agglomeration, India - Garima Nautiyal; Sandeep Maithani; Archana Sharma (Journal of the Indian Society of Remote Sensing, 2021)

A Novel Multi-Epitopic Peptide Vaccine Candidate Against Helicobacter pylori: In-Silico Identification, Design, Cloning and Validation Through Molecular Dynamics - Pratik Ghosh; Swarnav Bhakta; Manojit Bhattacharya; Ashish Ranjan Sharma; Garima Sharma; Sang-Soo Lee; Chiranjib Chakraborty (International Journal of Peptide Research and Therapeutics, 2021)

Characterization and diversity of Indian isolates of Ralstonia solanacearum inciting bacterial wilt of tomato - Dinesh Singh; Garima Chaudhary; D. K. Yadav (Indian Phytopathology, 2021)

Aerosols optical depth and Ångström exponent over different regions in Garhwal Himalaya, India - Amar Deep; Chhavi Pant Pandey; Hemwati Nandan; Narendra Singh; Garima Yadav; P. C. Joshi; K. D. Purohit; S. C. Bhatt (Environmental Monitoring and Assessment, 2021)

Differential Expression of Thymoquinone and Its Localization in Different Parts of Nigella sativa L. - Garima Gupta; Mohammed Shariq Iqbal; Brijesh Pandey; Janmejay Kumar Srivastava (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2021)

Antiviral Peptides: Identification and Validation - Garima Agarwal; Reema Gabrani (International Journal of Peptide Research and Therapeutics, 2021)

Membrane-embedded TSPO: an NMR view - Gwladys Rivière; Garima Jaipuria; Loren B. Andreas; Andrei Leonov; Karin Giller; Stefan Becker; Markus Zweckstetter (European Biophysics Journal, 2021)
Translocator Protein (18 kDa) (TSPO) is a mitochondrial transmembrane protein commonly used as a biomarker for neuroinflammation and is also a potential therapeutic target in neurodegenerative diseases. Despite intensive research efforts, the function of TSPO is still largely enigmatic. Deciphering TSPO structure in the native lipid environment is essential to gain insight into its cellular activities and to design improved diagnostic and therapeutic ligands. Here, we discuss the influence of lipid composition on the structure of mammalian TSPO embedded into lipid bilayers on the basis of solid-state NMR experiments. We further highlight that cholesterol can influence both the tertiary and quaternary TSPO structure and also influence TSPO localization in mitochondria-associated endoplasmic reticulum membranes.

Biological-based methods for the removal of volatile organic compounds (VOCs) and heavy metals - Mukesh Meena; Priyankaraj Sonigra; Garima Yadav (Environmental Science and Pollution Research, 2021)

Comparative Analysis and Molecular Evolution of Class I PI3K Regulatory Subunit p85α Reveal the Structural Similarity Between nSH2 and cSH2 Domains - Chiranjib Chakraborty; Ashish Ranjan Sharma; Garima Sharma; Sang-Soo Lee (International Journal of Peptide Research and Therapeutics, 2020)

Insight into Evolution and Conservation Patterns of B1-Subfamily Members of GPCR - Chiranjib Chakraborty; Ashish Ranjan Sharma; Garima Sharma; Manojit Bhattacharya; Sang-Soo Lee (International Journal of Peptide Research and Therapeutics, 2020)

Identification and Design of a Next-Generation Multi Epitopes Bases Peptide Vaccine Candidate Against Prostate Cancer: An In Silico Approach - Prasanta Patra; Manojit Bhattacharya; Ashish Ranjan Sharma; Pratik Ghosh; Garima Sharma; Bidhan Chandra Patra; Bidyut Mallick; Sang-Soo Lee; Chiranjib Chakraborty (Cell Biochemistry and Biophysics, 2020)

Investigating the Effect of Lockdown During COVID-19 on Land Surface Temperature: Study of Dehradun City, India - Sandeep Maithani; Garima Nautiyal; Archana Sharma (Journal of the Indian Society of Remote Sensing, 2020)

First record of off-season flowering in Populus deltoides from India: paradigm of climate change indicator - Garima Thapliyal; Ramu S. Vemanna; Prashant Mohan Pawar; Santan Barthwal; Rajendra K. Meena; Shailesh Pandey; Maneesh S. Bhandari (International Journal of Biometeorology, 2020)

Variation of carbonaceous species and trace elements in PM10 at a mountain site in the central Himalayan region of India - S. K. Sharma; Nikki Choudhary; Priyanka Srivastava; Manish Naja; N. Vijayan; Garima Kotnala; T. K. Mandal (Journal of Atmospheric Chemistry, 2020)

Emergence of Blue Sky Over Delhi Due to Coronavirus Disease (COVID-19) Lockdown Implications - Garima Kotnala; T. K. Mandal; S. K. Sharma; R. K. Kotnala (Aerosol Science and Engineering, 2020)

A Review of the Varied Uses of Macroalgae as Dietary Supplements in Selected Poultry with Special Reference to Laying Hen and Broiler Chickens - Garima Kulshreshtha; Maxwell T. Hincke; Balakrishnan Prithiviraj; Alan Critchley (Journal of Marine Science and Engineering, 2020)
Seaweeds comprise ca. 12,000 species. Global annual harvest is ca. 30.13 million metric tonnes, (valued ca. $11.7 billion USD in 2016) for various commercial applications. The growing scope of seaweed-based applications in food, agricultural fertilizers, animal feed additives, pharmaceuticals, cosmetics and personal care is expected to boost market demand. Agriculture and animal feed applications held the second largest seaweed market share in 2017, and the combined market is anticipated to reach much higher values by 2024 due to the impacts of current research and development targeting enhanced animal health and productivity. In general, seaweeds have been utilized in animal feed as a rich source of carbohydrates, protein, minerals, vitamins and dietary fibers with relatively well-balanced amino acid profiles and a unique blend of bioactive compounds. Worldwide, the animal nutrition market is largely driven by rising demand for poultry feeds, which represents ca. 47% of the total consumption for all animal nutrition. This review provides an overview of the utilization of specific seaweeds as sustainable feed sources for poultry production, including a detailed survey of seaweed-supplemented diets on growth, performance, gastrointestinal flora, disease, immunity and overall health of laying/broiler hens. Anti-microbial effects of seaweeds are also discussed.

Antimicrobial Effects of Selected, Cultivated Red Seaweeds and Their Components in Combination with Tetracycline, against Poultry Pathogen Salmonella Enteritidis - Garima Kulshreshtha; Alan Critchley; Bruce Rathgeber; Glenn Stratton; Arjun H. Banskota; Jeff Hafting; Balakrishnan Prithiviraj (Journal of Marine Science and Engineering, 2020)
Poultry and its products are an economical source of high-quality protein for human consumption. In animal agriculture, antibiotics are used as therapeutic agents to treat disease in livestock, or as prophylactics to prevent disease and in so doing enhance production. However, the extensive use of antibiotics in livestock husbandry has come at the cost of increasingly drug-resistant bacterial pathogens. This highlights an urgent need to find effective alternatives to be used to treat infections, particularly in poultry and especially caused by drug-resistant Salmonella strains. In this study, we describe the combined effect of extracts of the red seaweeds Chondrus crispus (CC) and Sarcodiotheca gaudichaudii (SG) and compounds isolated from these in combinations with industry standard antibiotics (i.e., tetracycline and streptomycin) against Salmonella Enteritidis. Streptomycin exhibited the higher antimicrobial activity against S. Enteritidis, as compared to tetracycline with a MIC25 and MIC50 of 1.00 and 1.63 μg/mL, respectively. The addition of a water extract of CC at a concentration of 200 µg/mL in addition to tetracycline significantly enhanced the antibacterial activity (log CFU/mL 4.7 and 4.5 at MIC25 and MIC50, respectively). SG water extract, at 400 and 800 µg/mL (p = 0.05, n = 9), also in combination with tetracycline, showed complete inhibition of bacterial growth. Combinations of floridoside (a purified red seaweed component) and tetracycline (MIC25 and MIC50) in vitro revealed that only the lower concentration (i.e., 15 μg/mL) of floridoside potentiated the activity of tetracycline. Sub-lethal concentrations of tetracycline (MIC50 and MIC25), in combination with floridoside, exhibited antimicrobial activities that were comparable to full-strength tetracycline (23 μg/mL). Furthermore, the relative transcript levels of efflux-related genes of S. Enteritidis, namely marA, arcB and ramA, were significantly repressed by the combined treatment of floridoside and tetracycline, as compared to control MIC treatments (MIC25 and MIC50). Taken together, these findings demonstrated that the red seaweeds CC and SG and their selected, purified components can be used to increase the lifetime of existing, patented antibiotics and can also help to reduce costly (economic and environmental) therapeutic and prophylactic use of antibiotics in poultry. To our knowledge, this is the first report of antibiotic potentiation of existing industry standard antibiotics using red seaweeds and their selected extracts against S. Enteritidis.

Synergistic antibacterial and anti-biofilm activity of nisin like bacteriocin with curcumin and cinnamaldehyde against ESBL and MBL producing clinical strains - Garima Sharma; Shweta Dang; Aruna K; Manjula Kalia; Reema Gabrani (Biofouling, 2020)

Characterization of exotic germplasm lines for resistance to wheat rusts and spot blotch - Satish Kumar; Garima Singroha; S. C. Bhardwaj; M. S. Saharan; O. P. Gangwar; C. N. Mishra; Anwar Khan; Sunita Mahapatra; M. Sivasamy; Ravish Chatrath; G. P. Singh (Indian Phytopathology, 2020)

Execution of programmed cell death by singlet oxygen generated inside the chloroplasts of Arabidopsis thaliana - Vivek Ambastha; Garima Chauhan; Budhi Sagar Tiwari; Baishnab C Tripathy (Protoplasma, 2020)

Study of Urban Growth Dynamics Using Global Human Settlement Layer Data Set: Uttarakhand, India - Garima Nautiyal; Sandeep Maithani; Archana Sharma (Journal of the Indian Society of Remote Sensing, 2020)

Postnatal zinc or paraquat administration increases paraquat or zinc-induced loss of dopaminergic neurons: insight into augmented neurodegeneration - Namrata Mittra; Amit Kumar Chauhan; Garima Singh; Devendra Kumar Patel; Chetna Singh (Molecular and Cellular Biochemistry, 2020)

Correction to: Prevalence and correlates of household food insecurity in Delhi and Chennai, India - Garima Rautela; Mohammed K. Ali; Dorairaj Prabhakaran; K.M. Venkat Narayan; Nikhil Tandon; Viswanathan Mohan; Lindsay M. Jaacks (Food Security, 2020)

Prevalence and correlates of household food insecurity in Delhi and Chennai, India - Garima Rautela; Mohammed K. Ali; Dorairaj Prabhakaran; K.M. Venkat Narayan; Nikhil Tandon; Viswanathan Mohan; Lindsay M. Jaacks (Food Security, 2020)

The DEAD-box RNA helicase eIF4A regulates plant development and interacts with the hnRNP LIF2L1 in Physcomitrella patens - Vidhi Tyagi; Vimala Parihar; Garima Malik; Vaibhav Kalra; Sanjay Kapoor; Meenu Kapoor (Molecular Genetics and Genomics, 2020)

Seasonal Variation of OC, EC, and WSOC of PM10 and Their CWT Analysis Over the Eastern Himalaya - Akansha Rai; Sauryadeep Mukherjee; Abhijit Chatterjee; Nikki Choudhary; Garima Kotnala; T. K. Mandal; S. K. Sharma (Aerosol Science and Engineering, 2020)

Spatial Variability and Sources of Atmospheric Ammonia in India: A Review - S. K. Sharma; Garima Kotnala; T. K. Mandal (Aerosol Science and Engineering, 2020)

Effects of geometry and rheological parameters of large basin on the SH-wave response of sub-basin in the basin-sub-basin models - J. P. Narayan; Garima Yadav (Journal of Seismology, 2020)

Dietary GABA enhances hypoxia tolerance of a bottom-dwelling carp, Cirrhinus mrigala by modulating HIF-1α, thyroid hormones and metabolic responses - Tincy Varghese; V. J Rejish Kumar; Garima Anand; Subrata Dasgupta; Asim Kumar Pal (Fish Physiology and Biochemistry, 2020)

The widely distributed legume tree Vachellia (Acacia) nilotica subsp. indica is nodulated by genetically diverse Ensifer strains in India - Sunil Choudhary; Nisha Tak; Garima Bissa; Bhawana Chouhan; Priyanka Choudhary; Janet I. Sprent; Euan K. James; Hukam S. Gehlot (Symbiosis, 2020)

Evaluation of COMT Gene rs4680 Polymorphism as a Risk Factor for Endometrial Cancer - Pradeep Kumar; Garima Singh; Vandana Rai (Indian Journal of Clinical Biochemistry, 2020)

Nested PCR assay for specific and sensitive detection of Alternaria carthami - Garima Anand; Rupam Kapoor (Archives of Microbiology, 2020)

Influence of Vehicular Emissions (NO, NO2, CO and NMHCs) on the Mixing Ratio of Atmospheric Ammonia (NH3) in Delhi, India - Garima Kotnala; S. K. Sharma; T. K. Mandal (Archives of Environmental Contamination and Toxicology, 2020)

Xenobiotic Binding Domain of Glutathione S-Transferase Has Cryptic Antimicrobial Peptides - Soyar Horam; Sneha Raj; Vikash Chandra Tripathi; Garima Pant; Mitra Kalyan; Thota Jagadeshwar Reddy; Jesu Arockiaraj; Mukesh Pasupuleti (International Journal of Peptide Research and Therapeutics, 2019)

Dicer 1 of Candida albicans cleaves plant viral dsRNA in vitro and provides tolerance in plants against virus infection - Chaudhary Mashhood Alam; Garima Jain; Aarzoo Kausar; Ashish Kumar Singh; Bikash Mandal; Anupam Varma; Choudhary Sharfuddin; Supriya Chakraborty (VirusDisease, 2019)

Multienvironmental evaluation of wheat (Triticum aestivum L.) germplasm identifies donors with multiple fungal disease resistance - Satish Kumar; Garima Singroha; S. C. Bhardwaj; Ritu Bala; M. S. Saharan; Vikas Gupta; Anwar Khan; Sunita Mahapatra; M. Sivasamy; Vijay Rana; C. N. Mishra; Om Prakash; et al. (Genetic Resources and Crop Evolution, 2019)

Identification of Rhizosphere Bacterial Diversity with Promising Salt Tolerance, PGP Traits and Their Exploitation for Seed Germination Enhancement in Sodic Soil - T. Damodaran; V. K. Mishra; S. K. Jha; Umesh Pankaj; Garima Gupta; Ram Gopal (Agricultural Research, 2019)

Genetics of ulcerative colitis: putting into perspective the incremental gains from Indian studies - Garima Juyal; Ajit Sood; Vandana Midha; B. K. Thelma (Journal of Genetics, 2018)

Synthesis, mechanistic and synergy studies of diarylidenecyclohexanone derivatives as new antiplasmodial pharmacophores - Bishnu P. Joshi; Dinesh Mohanakrishnan; Garima Mittal; Swayamsiddha Kar; Jeevan Kumar Pola; Nageswara Rao Golakoti; Jagadeesh Babu Nanubolu; Rajesh Babu D.; Sai Suraj Kumar S.; Dinkar Sahal (Medicinal Chemistry Research, 2018)

Population structure and virulence analysis of Alternaria carthami isolates of India using ISSR and SSR markers - Garima Anand; Rupam Kapoor (World Journal of Microbiology and Biotechnology, 2018)

RNAi-based transgene conferred extreme resistance to the geminivirus causing apical leaf curl disease in potato - Garima Tomar; S. K. Chakrabarti; Nitya Nanda Sharma; A. Jeevalatha; S. Sundaresha; Kanika Vyas; Wamik Azmi (Plant Biotechnology Reports, 2018)

Modeling Euglena sp. growth under different conditions using an artificial neural network - Garima Kishore; Abhijeet D. Kadam; Ujjwal Kumar; Kusum Arunachalam (Journal of Applied Phycology, 2018)

Association of DD genotype of angiotensin-converting enzyme gene (I/D) polymorphism with hypertension among a North Indian population - Garima Rana; Suniti Yadav; Shipra Joshi; K. N. Saraswathy (Journal of Community Genetics, 2018)

Allelopathic effects of exogenous phenylalanine: a comparison of four monocot species - Barbara R. Evans; Garima Bali; Art Ragauskas; Riddhi Shah; Hugh O’Neill; Cory Howard; Fayola Lavenhouse; Dawn Ramirez; Kelly Weston; Kelly Ramey; Valerie Cangemi; Brian Kinney; et al. (Planta, 2017)

Melioration in Anti-staphylococcal Activity of Conventional Antibiotic(s) by Organic Acids Present in the Cell Free Supernatant of Lactobacillus paraplantarum - Lavanya Rishi; Garima Mittal; Rajeev Kumar Agarwal; Taruna Sharma (Indian Journal of Microbiology, 2017)

Insight into the mechanisms of enhanced production of valuable terpenoids by arbuscular mycorrhiza - Rupam Kapoor; Garima Anand; Pooja Gupta; Shantanu Mandal (Phytochemistry Reviews, 2017)

In Vitro Selection of Cell Lines in Punica granatum L. (Daru) Against Bacterial Blight - Garima Kumari; Kamlesh Kanwar; Madhvi Soni; Deepika Sharma (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2017)

Guillain-Barre syndrome complicating chikungunya virus infection - Ayush Agarwal; Deepti Vibha; Achal Kumar Srivastava; Garima Shukla; Kameshwar Prasad (Journal of NeuroVirology, 2017)

Salinity induced differential methylation patterns in contrasting cultivars of foxtail millet (Setaria italica L.) - Garima Pandey; Chandra Bhan Yadav; Pranav Pankaj Sahu; Mehanathan Muthamilarasan; Manoj Prasad (Plant Cell Reports, 2017)

The crucial role and regulations of miRNAs in zebrafish development - Manojit Bhattacharya; Ashish Ranjan Sharma; Garima Sharma; Bidhan Chandra Patra; Ju-Suk Nam; Chiranjib Chakraborty; Sang-Soo Lee (Protoplasma, 2017)

Molecular identification of Thelandros scleratus and Thelastoma icemi (Nematoda: Oxyruida) using mitochondrial cox 1 sequences - Anshu Chaudhary; Garima Kansal; Neetu Singh; Kumari Shobhna; Manu Verma; Hridaya S. Singh (Acta Parasitologica, 2017)
Two species of parasitic nematodes collected from the intestine of Brook’s House Gecko,

A facile eco-friendly approach for the one-pot synthesis of 3,4-dihydro-2H-naphtho[2,3-e][1,3]oxazine-5,10-diones using glycerol as a green media - Shruti Gupta; Garima Khanna; Jitender M. Khurana (Environmental Chemistry Letters, 2016)

Plumbagin, a plant-derived naphthoquinone metabolite induces mitochondria mediated apoptosis-like cell death in Leishmania donovani: an ultrastructural and physiological study - Bhanu Priya Awasthi; Manoj Kathuria; Garima Pant; Neema Kumari; Kalyan Mitra (Apoptosis, 2016)

Analysis of bHLH coding genes using gene co-expression network approach - Swati Srivastava; Sanchita; Garima Singh; Noopur Singh; Gaurava Srivastava; Ashok Sharma (Molecular Biology Reports, 2016)

Nutritional and Sensory Properties of Vegetable Oil Filled Milk Beverage Prepared with Pulp of Mangifera indica L - Garima Singh; Ramesh Chandra; Chitranjan Kumar (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2016)

Scenario of organophosphate pollution and toxicity in India: A review - Shardendu Kumar; Garima Kaushik; Juan Francisco Villarreal-Chiu (Environmental Science and Pollution Research, 2016)

How methane feedback response influence redox processes in a tropical vertisol - Santosh Ranjan Mohanty; Sneh Tiwari; Garima Dubey; Usha Ahirwar; Bharati Kollah (Biology and Fertility of Soils, 2016)

A 12-Crown-4 Ether Containing Dipeptide Boc-12-Crown-4-l-DOPA-Gly-OMe Induces Cell Cycle Arrest and Apoptosis in Rat Eggs Cultured In Vitro - Garima Tripathi; Anima Tripathi; Gurunath Ramanathan; Shail K. Chaube (International Journal of Peptide Research and Therapeutics, 2016)

Influence of bioenergy crop Jatropha curcas amendment on soil biogeochemistry in a tropical vertisol - Bharati Kollah; Garima Dubey; Peter Dunfield; Santosh Ranjan Mohanty (Mitigation and Adaptation Strategies for Global Change, 2015)

Plantlet formation via somatic embryogenesis and LC ESI Q-TOF MS determination of secondary metabolites in Butea monosperma (Lam.) Kuntze - Chetan Sharma; Tejaswita Kumari; Garima Pant; Vikas Bajpai; Mukesh Srivastava; Kalyan Mitra; Brijesh Kumar; K. R. Arya (Acta Physiologiae Plantarum, 2015)

A snapshot of microbial communities from the Kutch: one of the largest salt deserts in the World - Aanal S. Pandit; Madhvi N. Joshi; Poonam Bhargava; Inayatullah Shaikh; Garima N. Ayachit; Sandeep R. Raj; Akshay K. Saxena; Snehal B. Bagatharia (Extremophiles, 2015)

Production of deuterated switchgrass by hydroponic cultivation - Barbara R. Evans; Garima Bali; Marcus Foston; Arthur J. Ragauskas; Hugh M. O’Neill; Riddhi Shah; Joseph McGaughey; David Reeves; Caroline S. Rempe; Brian H. Davison (Planta, 2015)

Synthesis, 3D-QSAR and docking studies of pyrimidine nitrile-pyrazoline: a novel class of hybrid antimalarial agents - Akranth Marella; Mymoona Akhter; Mohammad Shaquiquzzaman; Omprakash Tanwar; Garima Verma; Mohammad Mumtaz Alam (Medicinal Chemistry Research, 2015)

Eu3+, Yb3+ and Eu3+-Yb3+ Complexes with Salicylic Acid and 1,10-Phenanthroline: Synthesis, Photoluminescent Properties and Energy Transfer - Garima Sharma; Anudeep Kumar Narula (Journal of Fluorescence, 2015)

Changes in free radical generation, metabolites and antioxidant defense machinery in hyacinth bean (Lablab purpureus. L) in response to high temperature stress - Nagendra Rai; Krishna Kumar Rai; Garima Tiwari; Pramod Kumar Singh (Acta Physiologiae Plantarum, 2015)

Identification, Characterization and Expression Profiling of Dicer-Like, Argonaute and RNA-Dependent RNA Polymerase Gene Families in Foxtail Millet - Chandra Bhan Yadav; Mehanathan Muthamilarasan; Garima Pandey; Manoj Prasad (Plant Molecular Biology Reporter, 2015)

Methoxy Poly(ethylene glycol)-Poly(lactide) Nanoparticles Encapsulating Quercetin Act as an Effective Anticancer Agent by Inducing Apoptosis in Breast Cancer - Garima Sharma; Jongbong Park; Ashish Ranjan Sharma; Jun-Sub Jung; Haesung Kim; Chiranjib Chakraborty; Dong-Keun Song; Sang-Soo Lee; Ju-Suk Nam (Pharmaceutical Research, 2015)

Green synthesis, antibacterial activity, and SAR of some novel naphthalimides and allylidenes - Garima Kumari; Ramendra K. Singh (Medicinal Chemistry Research, 2015)

Erratum to: In silico study of binding motifs in squalene synthase enzyme of secondary metabolic pathway of solanaceae - Sanchita; Garima Singh; Ashok Sharma (Molecular Biology Reports, 2014)

In silico study of binding motifs in squalene synthase enzyme of secondary metabolic pathway solanaceae family - Sanchita; Garima Singh; Ashok Sharma (Molecular Biology Reports, 2014)

Population and genomic lessons from genetic analysis of two Indian populations - Garima Juyal; Mayukh Mondal; Pierre Luisi; Hafid Laayouni; Ajit Sood; Vandana Midha; Peter Heutink; Jaume Bertranpetit; B. K. Thelma; Ferran Casals (Human Genetics, 2014)

Sumoylation May Play an Important Role in Modification of Large Number of Proteins Associated with Heat Stress in Plants - Avantika Singh; Garima Vats; Nidhi Chandra; Monendra Grover (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2014)

Detection of Ralstonia solanacearum from Asymptomatic Tomato Plants, Irrigation Water, and Soil Through Non-selective Enrichment Medium with hrp Gene-Based Bio-PCR - Dinesh Singh; Shweta Sinha; D. K. Yadav; Garima Chaudhary (Current Microbiology, 2014)

Effect of Wheatgrass on Membrane Fatty Acid Composition During Hepatotoxicity Induced by Alcohol and Heated PUFA - Varalakshmi Durairaj; Garima Shakya; Sankar Pajaniradje; Rukkumani Rajagopalan (The Journal of Membrane Biology, 2014)

Object-shape recognition and 3D reconstruction from tactile sensor images - Anwesha Khasnobish; Garima Singh; Arindam Jati; Amit Konar; D. N. Tibarewala (Medical & Biological Engineering & Computing, 2014)

QTL Analysis of Late Blight Resistance in a Diploid Potato Family of Solanum spegazzinii × S. chacoense - S. K. Chakrabarti; B. P. Singh; Garima Thakur; Jagesh K. Tiwari; S. K. Kaushik; Sanjeev Sharma; Vinay Bhardwaj (Potato Research, 2014)

Gassericin A: a circular bacteriocin produced by Lactic acid bacteria Lactobacillus gasseri - Neha Pandey; R. K. Malik; J. K. Kaushik; Garima Singroha (World Journal of Microbiology and Biotechnology, 2013)

Population Genetic Study of Fagopyrum tataricum from Western Himalaya Using ISSR Markers - Garima Kishore; Anjana Pandey; Rajendra Dobhal; Sanjay Gupta (Biochemical Genetics, 2013)

Modeling analysis of potential carbon sequestration under existing agroforestry systems in three districts of Indo-gangetic plains in India - Ajit; S. K. Dhyani; Ramnewaj; A. K. Handa; Rajendra Prasad; Badre Alam; R. H. Rizvi; Garima Gupta; K. K. Pandey; Amit Jain; Uma (Agroforestry Systems, 2013)

Allelochemical resistance traits of muskmelon (Cucumis melo) against the fruit fly (Bactrocera cucurbitae) in a hot arid region of India - Shravan M. Haldhar; R. Bhargava; B. R. Choudhary; Garima Pal; Suresh Kumar (Phytoparasitica, 2013)

Epigenetic mechanisms of plant stress responses and adaptation - Pranav Pankaj Sahu; Garima Pandey; Namisha Sharma; Swati Puranik; Mehanathan Muthamilarasan; Manoj Prasad (Plant Cell Reports, 2013)

Predatory performance of aphidophagous ladybirds: a measure of prey suitability? - Bhupendra Kumar; Garima Pandey; Geetanjali Mishra; Omkar (International Journal of Tropical Insect Science, 2013)

Synthesis and in vitro antibacterial activity of schiff bases of N-substituted isatins as effective scaffolds - Garima Kumari; Ramendra K. Singh (Medicinal Chemistry Research, 2013)

Adsorption of colored pollutants from distillery spent wash by native and treated fungus: Neurospora intermedia - Garima Kaushik; Indu Shekhar Thakur (Environmental Science and Pollution Research, 2013)

Arsenite Tolerance is Related to Proportional Thiolic Metabolite Synthesis in Rice (Oryza sativa L.) - Richa Dave; Pradyumna Kumar Singh; Preeti Tripathi; Manju Shri; Garima Dixit; Sanjay Dwivedi; Debasis Chakrabarty; Prabodh Kumar Trivedi; Yogesh Kumar Sharma; Om Prakash Dhankher; Francisco Javier Corpas; Juan B. Barroso; et al. (Archives of Environmental Contamination and Toxicology, 2013)

Rodent Models and Contemporary Molecular Techniques: Notable Feats yet Incomplete Explanations of Parkinson’s Disease Pathogenesis - Sharawan Yadav; Anubhuti Dixit; Sonal Agrawal; Ashish Singh; Garima Srivastava; Anand Kumar Singh; Pramod Kumar Srivastava; Om Prakash; Mahendra Pratap Singh (Molecular Neurobiology, 2012)

Nickel and Ultraviolet-B Stresses Induce Differential Growth and Photosynthetic Responses in Pisum sativum L. Seedlings - Garima Srivastava; Sushil Kumar; Gunjan Dubey; Vagish Mishra; Sheo Mohan Prasad (Biological Trace Element Research, 2012)

Characterization of a Reuterin-Producing Lactobacillus reuteri BPL-36 Strain Isolated from Human Infant Fecal Sample - Santosh Kumar Mishra; R. K. Malik; G. Manju; Neha Pandey; Garima Singroha; Pradip Behare; J. K. Kaushik (Probiotics and Antimicrobial Proteins, 2012)

DNA-energetics-based analyses suggest additional genes in prokaryotes - Garima Khandelwal; Jalaj Gupta; B Jayaram (Journal of Biosciences, 2012)

Transformation of pWWO in Rhizobium leguminosarum DPT to Engineer Toluene Degrading Ability for Rhizoremediation - Garima Goel; Piyush Pandey; Anchal Sood; Sandeep Bisht; D. K. Maheshwari; G. D. Sharma (Indian Journal of Microbiology, 2012)

Optimization Studies on Gastroretentive Floating System Using Response Surface Methodology - Rajendra Awasthi; Giriraj T. Kulkarni; Vivek K. Pawar; Garima Garg (AAPS PharmSciTech, 2012)

Melatonin as a Neuroprotective Agent in the Rodent Models of Parkinson’s Disease: Is it All Set to Irrefutable Clinical Translation? - Naveen Kumar Singhal; Garima Srivastava; Sonal Agrawal; Swatantra Kumar Jain; Mahendra Pratap Singh (Molecular Neurobiology, 2012)

A short survey on protein blocks - Agnel Praveen Joseph; Garima Agarwal; Swapnil Mahajan; Jean-Christophe Gelly; Lakshmipuram S. Swapna; Bernard Offmann; Frédéric Cadet; Aurélie Bornot; Manoj Tyagi; Hélène Valadié; Bohdan Schneider; Catherine Etchebest; et al. (Biophysical Reviews, 2010)

Chitinolytic Activity of Cold Tolerant Antagonistic Species of Streptomyces Isolated from Glacial Sites of Indian Himalaya - Mukesh K. Malviya; Anita Pandey; Pankaj Trivedi; Garima Gupta; Bhavesh Kumar (Current Microbiology, 2009)

Toward a Fuzzy Logic Control of the Infant Incubator - Narender P. Reddy; Garima Mathur; S. I. Hariharan (Annals of Biomedical Engineering, 2009)

Probing into the role of conserved N-glycosylation sites in the Tyrosinase glycoprotein family - Garima Gupta; Sharmistha Sinha; Nivedita Mitra; Avadhesha Surolia (Glycoconjugate Journal, 2009)

Isolation of fungi and optimization of process parameters for decolorization of distillery mill effluent - Garima Kaushik; Indu Shekhar Thakur (World Journal of Microbiology and Biotechnology, 2009)

Regeneration of static-load-degenerated articular cartilage extracellular matrix by vitamin C supplementation - Garima Sharma; R. K. Saxena; Prashant Mishra (Cell and Tissue Research, 2009)

Geo-spatial approach for phytodiversity characterization in Panna National Park (part), M.P. (India) - Garima Porwal; Sarnam Singh (Journal of the Indian Society of Remote Sensing, 2009)

Defining substrate interactions with calreticulin: an isothermal titration calorimetric study - Garima Gupta; Emiliano Gemma; Stefan Oscarson; Avadhesha Surolia (Glycoconjugate Journal, 2008)

Regeneration of static-load-degenerated articular cartilage extracellular matrix by vitamin C supplementation - Garima Sharma; R. K. Saxena; Prashant Mishra (Cell and Tissue Research, 2008)

Assessing toxicity of post-emergence herbicides to the Spilarctia obliqua Walker (Lepidoptera: Arctiidae) - Garima Gupta; A. K. Bhattacharya (Journal of Pest Science, 2008)

NMR studies on the conformation of oligomannosides and their interaction with banana lectin - Caroline Clavel; Angeles Canales; Garima Gupta; J. Ignacio Santos; F. Javier Cañada; Soledad Penadés; Avadesha Surolia; Jesús Jiménez-Barbero (Glycoconjugate Journal, 2007)

Characterization of protein transacetylase from human placenta as a signaling molecule calreticulin using polyphenolic peracetates as the acetyl group donors - Seema; Ranju Kumari; Garima Gupta; Daman Saluja; Ajit Kumar; Sanjay Goel; Yogesh K. Tyagi; Ruchika Gulati; Anjali Vinocha; Kambadoor Muralidhar; Bilikere S. Dwarakanth; Ramesh C. Rastogi; et al. (Cell Biochemistry and Biophysics, 2007)

Unbiased membrane permeability parameters for gabapentin using boundary layer approach - Jitender Madan; Garima Chawla; Vinod Arora; Rajiv Malik; Arvind K. Bansal (The AAPS Journal, 2005)

Breast cancer in developing population: A nutrition caveat - Garima Mehta; Seema Kothari; P. P. Singh (Indian Journal of Clinical Biochemistry, 2001)